Hybrid solid-state ionic conductor, solid-state electrolyte, positive electrode and electrochemical device including same, and method for preparing hybrid solid-state ionic conductor

By adopting mixed solid ion conductors composed of specific compounds and salts, the problems of insufficient ion conductivity and charging/discharge characteristics in the prior art are solved, and electrochemical performance with high energy density and safe operation are achieved.

CN119725696APending Publication Date: 2025-03-28SAMSUNG SDI CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411338974.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-09-26
Filing Date
2024-09-25
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Existing solid-state ion conductors have shortcomings in ion conductivity and charging/discharge characteristics, and it is difficult to meet the needs of high energy density and safe operation.

Method used

A mixed solid ion conductor consisting of specific compounds and salts, including compounds and salts represented by formulas 1 and 2, is prepared by mechanical grinding and molding methods.

Benefits of technology

It improves ion conductivity and charging/discharge characteristics, provides improved electrochemical performance, and is suitable for electrochemical devices such as all-solid-state secondary batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725696A_ABST
    Figure CN119725696A_ABST
Patent Text Reader

Abstract

The invention relates to a mixed solid-state ionic conductor, a solid-state electrolyte, a positive electrode and an electrochemical device including the same, and a method for preparing the mixed solid-state ionic conductor. The mixed solid-state ion conductor includes: a compound represented by Formula 1; and a salt represented by Formula 2: wherein in Formula 1 and Formula 2, M, M ', M' ', X, Y', Z, a, b, c, d, e, f, and g are as described in the specification. # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application is based on and claims the benefit of priority from Korean Patent Application No. 10-2023-0129565 filed in the Korean Intellectual Property Office on September 26, 2023, and all rights and interests arising therefrom, the contents of which are incorporated herein in their entirety by reference. Technical Field

[0003] The present disclosure relates to hybrid solid-state ion conductors, solid-state electrolytes, positive electrodes and electrochemical devices including the hybrid solid-state ion conductors, and methods for preparing the hybrid solid-state ion conductors. Background Art

[0004] In order to achieve high energy density, electrochemical devices such as all-solid-state secondary batteries use lithium metal or the like as a negative electrode, and use a solid-state ion conductor as an electrolyte for safe operation.

[0005] Depending on the type of anion, oxide-based (i.e., containing oxide) solid-state ion conductors, sulfide-based (i.e., containing sulfide) solid-state ion conductors, and halide-based (i.e., containing halide) solid-state ion conductors have been widely studied as solid-state ion conductors. However, although oxide-based solid-state ion conductors have high chemical stability, they have lower performance than sulfide-based solid-state ion conductors in terms of ionic conductivity and formability. Sulfide-based solid-state ion conductors have high ionic conductivity and good formability (moldability), but react with water to produce toxic gases. Halide-based solid-state ion conductors do not produce toxic gases and are highly adaptable to the environment, but they still have unsatisfactory ionic conductivity and lack stability during battery assembly.

[0006] Therefore, there remains a need for new compositions of solid-state ion conductors having improved ionic conductivity and improved charge / discharge characteristics. Summary of the invention

[0007] Provided are hybrid solid-state ion conductors having improved ionic conductivity and improved charge and discharge characteristics.

[0008] A solid electrolyte including the hybrid solid-state ion conductor is provided.

[0009] A positive electrode including the hybrid solid-state ion conductor is provided.

[0010] An electrochemical device including the hybrid solid-state ion conductor is provided.

[0011] A method for preparing the hybrid solid-state ion conductor is provided.

[0012] Additional aspects will be set forth in part in the description which follows and, in part, will be apparent from the description, or may be learned by practice of the presented embodiments of the disclosure.

[0013] According to one aspect of the present disclosure, a hybrid solid-state ion conductor includes: a compound represented by Formula 1; and a salt represented by Formula 2,

[0014] Formula 1

[0015] M a M' b X c Y' d Z e

[0016] In formula 1,

[0017] M is an alkali metal having an oxidation number of +1,

[0018] M' is one or more metal cations having an oxidation number of +2, +3, +4, +5, or +6,

[0019] X is one or more of halogen anions having an oxidation number of -1,

[0020] Y' is an anion having an oxidation number of -1,

[0021] Z is an anion having an oxidation number of -3,

[0022] 0.5 ≤ a ≤ 7, 0.5 ≤ b ≤ 2, 0 < c ≤ 6, 0 ≤ d ≤ 6, 0 ≤ e ≤ 6, and

[0023] 0 < c + d + e ≤ 6, and

[0024] Formula 2

[0025] M" f (PO4) g

[0026] In Formula 2,

[0027] M" is the same metal cation as M' in Formula 1, or a different metal cation having an oxidation number of +2, +3, +4, +5, or +6 and having an ionic radius within ±10% of the ionic radius of M', and

[0028] 0 < f ≤ 3, and 0 < g ≤ 10.

[0029] According to an embodiment, the ion radius of the metal cation of M' in Formula 1 may be 70 picometers to 100 picometers.

[0030] According to an embodiment, M' in Formula 1 may be a cation of one or more metals selected from the group consisting of Ti, Zr, Hf, V, Nb, Ta, Al, Ga, In, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Y, or Lu.

[0031] According to an embodiment, Y' in Formula 1 may be one or more of the following anions: SO3 - 、CH3COO - , CN - 、NO3 - 、NO2 - 、H2PO4 - PF6 - OH - 、BF4 - 、N(CF3SO2)2 - CF3CO2 - CF3SO3 - 、C(CF3SO2)3 - 、HCO3 - 、ClO4 - 、HSO4 - , or SCN - .

[0032] According to an embodiment, Z in Formula 1 may be one or more of the following anions: (BO4) 3- 、(BO3) 3- 、(PO4) 3- , [Fe(CN)6] 3- , or [Ag(S2O3)2] 3- .

[0033] According to an embodiment, impurities (eg, the first component) may not be included.

[0034] According to an embodiment, impurities may be further included in an amount of greater than about 0 wt % and less than about 5 wt % based on 100 wt % of the total amount of the hybrid solid-state ion conductor.

[0035] According to an embodiment, the impurity may include one or more of the following: a compound represented by Formula 3, a salt represented by Formula 4, or a combination thereof,

[0036] Formula 3

[0037] (M1) p (X1) q (Y'1) r (Z1) s

[0038] in

[0039] M1 may be one or more metal cations having an oxidation number of +2, +3, +4, +5, or +6,

[0040] X1 may be one or more of halogen anions having an oxidation number of -1,

[0041] Y'1 may be an anion having an oxidation number of -1,

[0042] Z1 may be an anion having an oxidation number of -3, and

[0043] 0.5 ≤ p ≤ 2, 0 < q ≤ 6, 0 ≤ r ≤ 6, 0 ≤ s ≤ 6, and 0 < q + r + s ≤6.

[0044] Formula 4

[0045] (M2) t (PO4) v

[0046] in

[0047] M2 may be an alkali metal having an oxidation number of +1,

[0048] 0.5 ≤ t ≤ 7, and 0 < v ≤ 7 / 3.

[0049] According to embodiments, the compound of Formula 1 and the salt of Formula 2 may each be a nanoparticle having a particle size of about 1 nm to about 100 nm.

[0050] According to an embodiment, the hybrid solid-state ion conductor may have a distorted rocksalt type crystal structure.

[0051] According to an embodiment, the compound of Formula 1 has an octahedral structure in which M' is a central metal cation coordinated with six X halogen anions, or in which M' is a central metal cation coordinated with six X halogen anions, some of which are replaced by one or more of the anions of Y' and Z, and the salt of Formula 2 may be located in the space around the octahedral structure.

[0052] According to an embodiment, the hybrid solid-state ion conductor may have a layered crystal structure.

[0053] According to an embodiment, the amount of the salt of Formula 2 may be about 5 weight percent (wt %) to about 30 wt % based on 100 wt % of the total weight of the hybrid solid-state ion conductor.

[0054] According to an embodiment, the hybrid solid-state ion conductor may have a conductivity of about 8.0 x 10 -4 Siemens / cm (S cm -1 ) to about 3.0 x 10 -3 S cm -1 ion conductivity.

[0055] According to another aspect of the present disclosure, a solid-state electrolyte includes the mixed solid-state ion conductor described above.

[0056] According to another aspect of the present disclosure, a positive electrode includes the mixed solid-state ion conductor described above.

[0057] According to another aspect of the present disclosure, an electrochemical device comprises:

[0058] positive electrode layer;

[0059] a cathode layer; and

[0060] a solid electrolyte layer between the positive electrode layer and the negative electrode layer,

[0061] The solid electrolyte as described above is in at least one of the positive electrode layer, the negative electrode layer, and the solid electrolyte layer.

[0062] According to an embodiment, the positive electrode layer may include the solid electrolyte, and the solid electrolyte layer includes: a first solid electrolyte including the solid electrolyte described above, and a second solid electrolyte including a sulfide-containing solid electrolyte, an oxide-containing solid electrolyte, a polymer solid electrolyte, or a combination thereof.

[0063] The electrochemical device may be an electrochemical cell, a battery, a supercapacitor, a fuel cell, a sensor, or a color changing device.

[0064] According to another aspect of the present disclosure, a method for manufacturing a hybrid solid-state ion conductor includes: providing a precursor and a salt for forming a solid-state ion conductor; mechanically grinding the precursor and the salt to provide a precursor mixture; and shaping (molding) the precursor mixture to prepare the hybrid solid-state ion conductor. BRIEF DESCRIPTION OF THE DRAWINGS

[0065] The above and other aspects, features and advantages of some embodiments of the present disclosure will become more apparent from the following description considered in conjunction with the accompanying drawings, in which:

[0066] Figure 1A is a schematic diagram showing an embodiment of a crystal structure of a hybrid solid-state ion conductor;

[0067] Figure 1B is a schematic diagram showing an embodiment of a crystal structure of a hybrid solid-state ion conductor;

[0068] Figure 2 is a schematic diagram showing an embodiment of a unit cell in a crystal structure of a hybrid solid-state ion conductor;

[0069] Figures 3 to 5 Each is a cross-sectional view of an embodiment of an all-solid-state secondary battery;

[0070] Figure 6 is a graph of intensity (arbitrary units, au) versus diffraction angle (° 2θ) and shows the results of X-ray diffraction (XRD) analysis using CuKα radiation for the hybrid solid-state ion conductor prepared in Example 1 and Zr3(PO4)4;

[0071] Figure 7 is the imaginary impedance (Z'', ohm square centimeter, Ω cm 2 ) for real impedance (Z', Ω·cm 2 ), which shows the impedance measurement results of lithium symmetric batteries having a lithium / solid electrolyte / lithium structure manufactured using the (mixed) solid ion conductor discs prepared in Example 1 and Comparative Example 1 as solid electrolytes;

[0072] Figure 8 is the conductivity (Siemens / cm, S·cm -1 ) to 1000 / temperature (T) (reciprocal of Kelvin, K -1 ) and shows the activation energy (E ) obtained by electrochemical impedance spectroscopy (EIS) analysis of the platinum (Pt) electrode structure formed on the surface of the (hybrid) solid ion conductor disc prepared according to Example 1 and Comparative Example 1. a ) value; and

[0073] Fig. 9A and 9B The voltage (V) is plotted against the capacity (mAh / cm2). 2 ) and respectively show the initial charge and discharge test results of the all-solid-state secondary batteries manufactured in Example 6 and Comparative Example 17. DETAILED DESCRIPTION

[0074] Embodiments will now be described in detail, examples of which are shown in the accompanying drawings, wherein the same reference numerals refer to the same elements throughout. In this regard, the present embodiment may have different forms and should not be construed as being limited to the description set forth herein. Therefore, the following only describes the embodiments to illustrate aspects by reference to the accompanying drawings. As used herein, the term "and / or" includes any and all combinations of one or more of the related enumerated items. Statements such as "at least one (kind)" when before or after a list of elements modify the entire list of elements and do not modify a single element of the list.

[0075] The inventive concept described below can be modified in many ways and can have many examples, and therefore, some examples are shown in the drawings and described in detail in the specification. However, the inventive concept should not be interpreted as being limited to the example embodiments set forth herein, and on the contrary, should be interpreted as covering all modifications, equivalents, or substitutes included within the scope of the inventive concept.

[0076] The terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the inventive concept. An expression used in the singular encompasses the expression in the plural unless it has an obviously different meaning in the context.

[0077] The term used herein is only used for the purpose of describing specific embodiments, and is not intended to be restrictive. As used herein, "one (kind) (indefinite article) (a, an)", "said (the)" and "at least one (kind)" do not represent the limitation of quantity, and include both singular and plural numbers, unless the context clearly indicates otherwise. For example, "element" has the same meaning as "at least one element", unless the context clearly indicates otherwise. Therefore, in the claim, mentioning ("one (indefinite article) (an)") element and then mentioning "said" element includes one element and multiple elements. "At least one (kind)" will not be interpreted as limiting "one (kind)". "Or" means "and / or". As used herein, the term "and / or" includes any and all combinations of one or more of the related enumerated items. It will be further understood that the term "comprising" or "including" when used in this specification, indicates that there are stated features, regions, wholes, steps, operations, elements and / or components, but does not exclude the presence or addition of one or more other features, regions, wholes, steps, operations, elements, components, and / or its set.

[0078] In this specification, the expression "at least one type", "one or more types", or "one or more" before a component (component) may supplement the entire component (component) list and may not supplement the individual component (component) described. For example, "at least one of A, B, and C" and similar phrases (e.g., "at least one selected from A, B, and C" or "one or more selected from A, B, and C") are interpreted as A alone, B alone, C alone, or a combination of at least two or more of A, B, and C, such as ABC, AB, BC, and AC.

[0079] The term "combination" used herein includes mixtures, alloys, reaction products, etc., unless otherwise specifically stated. The term "comprising" used herein means further including other components (components), rather than excluding other components (components), unless otherwise specifically stated.

[0080] The term "first" and "second" do not represent order, amount, or importance, but are used to distinguish an element from other elements. It will be understood that although the terms "first", "second", "third", etc. can be used to describe various elements, components, regions, layers, and / or parts in this article, these elements, components, regions, layers, and / or parts should not be limited by these terms. These terms are only used to distinguish an element, component, region, layer or part from other elements, components, regions, layers or parts. Therefore, without departing from the teachings herein, the "first element", "component", "region", "layer" or "part" discussed below may be referred to as the second element, component, region, layer or part. Unless otherwise specified herein or clearly contradictory to the context, it should be interpreted as including both the singular and the plural. "Or" refers to "and / or", unless otherwise specified.

[0081] In this specification, a component described with reference to another component using expressions “on,” “over,” etc. may be positioned in direct contact with the other component, or a component may be interposed therebetween.

[0082] Throughout this specification, "(an) embodiment," "an embodiment," etc. refer to situations in which a particular element described with respect to an embodiment is included in at least one embodiment described herein and may or may not be present in other embodiments. In addition, it should be understood that the described elements may be combined in any suitable manner in the various embodiments.

[0083] In addition, relative terms such as "lower" or "bottom" and "upper" or "top" may be used herein to describe the relationship of one element to another element as shown in the figure. It will be understood that in addition to the directions shown in the figures, relative terms are also intended to cover different directions of the device. For example, if the device in one of the figures is turned over, the element described as "on the "lower" side of the other element will be oriented on the "upper" side of the other element. Therefore, the term "lower" can cover both "lower" and "upper" directions depending on the specific direction of the figure. Similarly, if the device in one of the figures is turned over, the element described as "below" or "below" the other element will be oriented "above" the other element. Therefore, the term "below..." or "below..." can cover both "above..." and "below..." directions.

[0084] Unless otherwise stated, all percentages, parts, ratios, etc. are based on weight. In addition, when an amount, concentration, or other value or parameter is given as a range, a preferred range, or one of a preferred upper and lower limit, it should be understood that these cases can include all ranges formed by any upper range limit and any lower range limit, or any pair of preferred values, regardless of whether the range is disclosed separately.

[0085] When a range of values ​​is stated herein, unless otherwise stated, the range is intended to include the endpoints and all integers and fractions within the range. It is not intended that the scope of the present disclosure be limited to the specific values ​​recited when defining a range.

[0086] Unless otherwise specifically stated, the unit "parts by weight" refers to a weight ratio between corresponding components, and the unit "parts by mass" refers to a value obtained by converting the weight ratio of the corresponding components into a solid content.

[0087] The terms "about", "approximately" or "substantially" used herein include the stated values ​​and refer to within an acceptable deviation range from the specific value as determined by a person skilled in the art taking into account the measurement-related errors and the measurement of the specific amount (i.e., the limitations of the measurement system). For example, "about", "approximately" or "substantially" may refer to within one or more standard deviations relative to a specified value, or within ± 30%, 20%, 10%, or 5%. All ranges disclosed herein include endpoints, and the endpoints are independently combinable with each other (e.g., the range of "up to 25% by weight, or more particularly 5% to 20% by weight" includes all intermediate values ​​of the range of endpoints and "5% to 25% by weight", etc.).

[0088] Unless otherwise defined, all terms (including technical terms and scientific terms) used in this specification have the same meanings as those commonly understood by those of ordinary skill in the art to which the present disclosure belongs. It will also be understood that terms, such as those commonly used and defined in dictionaries, should be interpreted as having meanings consistent with their meanings in the context of the relevant art and the present disclosure, and will not be interpreted as idealized. In addition, they should not be interpreted in an overly formal sense.

[0089] Example embodiments are described herein with reference to cross-sectional views that are schematic diagrams of idealized embodiments. Therefore, the shape of the embodiment may change, for example, as a result of manufacturing techniques and / or tolerances. Therefore, the embodiments described herein should not be interpreted as being limited to the specific shapes of the regions as described herein, but should include deviations in shape that occur, for example, during manufacturing. For example, a region illustrated or described as flat may typically have rough and / or nonlinear features. In addition, the illustrated sharp corners may be rounded. Therefore, the regions illustrated in the figures are schematic in nature, and their shapes are not intended to illustrate the precise shape of the region or to limit the scope of the claims.

[0090] Generally, electrochemical devices that do not use liquid electrolytes, such as all-solid-state secondary batteries, have minimal safety issues due to flammability and evaporation, and minimal decomposition issues due to reactions with lithium metal. However, the solid electrolytes that constitute all-solid-state secondary batteries cannot achieve high ion conductivity like liquid electrolytes. Therefore, compared with lithium-ion batteries, all-solid-state secondary batteries are inferior in charge and discharge characteristics.

[0091] Recently, halide-based solid ion conductors have attracted attention as solid ion conductors used as solid electrolytes. Halide-based solid electrolytes are mechanically flexible, non-flammable, and can be formed (molded) in a variety of ways by simple pressing. Li3InCl6 or Li3YCl6 are examples of known halide-based solid electrolytes. However, even with such halide-based solid electrolytes, satisfactory levels of ionic conductivity and battery stability cannot be achieved, and therefore, the desired level of charge and discharge characteristics cannot be obtained.

[0092] In order to solve the above problems, the inventors of the present application have proposed a solid-state ion conductor of a novel composition, a solid-state electrolyte, a positive electrode and an electrochemical device thereof, and a method for manufacturing the above-mentioned solid-state ion conductor.

[0093] Hereinafter, a solid-state ion conductor, a solid-state electrolyte, a positive electrode, and an electrochemical device including the same, and a method of manufacturing the solid-state ion conductor will be described in more detail through embodiments.

[0094] Solid state ion conductors

[0095] According to an embodiment, the hybrid solid-state ion conductor includes a compound represented by Formula 1 and a salt represented by Formula 2:

[0096] Formula 1

[0097] M a M' b X c Y' d Z e

[0098] in

[0099] M may be an alkali metal having an oxidation number of +1,

[0100] M' may be one or more metal cations having an oxidation number of +2, +3, +4, +5, or +6,

[0101] X may be one or more of a halogen anion having an oxidation number of -1,

[0102] Y' may be an anion having an oxidation number of -1,

[0103] Z may be an anion having an oxidation number of -3,

[0104] 0.5 ≤ a ≤ 7, 0.5 ≤ b ≤ 2, 0 < c ≤ 6, 0 ≤ d ≤ 6, 0 ≤ e ≤ 6, and

[0105] 0 < c + d + e ≤ 6, and

[0106] Formula 2

[0107] M" f (PO4) g

[0108] wherein M" may be the same metal cation as M' in Formula 1, or a different metal cation having an oxidation number of +2, +3, +4, +5, or +6 and having an ionic radius within ±10% of the ionic radius of M', and

[0109] 0 < f ≤ 3, and 0 < g ≤ 10.

[0110] Regarding the compound of Formula 1, according to embodiments, M may be one or more of alkali metals of lithium (Li), sodium (Na), potassium (K), rubidium (Rb), cesium (Cs), or francium (Fr).

[0111] According to an embodiment, M' may be one or more metal cations having an oxidation number of +2, +3, +4, +5, or +6 excluding alkali metal cations. For example, M' may be one or more metal cations having an oxidation number of +3, +4, or +5.

[0112] According to embodiments, the ionic radius of the metal cation of M' may be 70 picometers to 100 picometers.

[0113] According to an embodiment, M' may be a cation of one or more of Ti, Zr, Hf, V, Nb, Ta, Al, Ga, In, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Y, or Lu.

[0114] According to an embodiment, X may be one or more of the halogen anions of fluorine (F), chlorine (Cl), bromine (Br), or iodine (I). For example, X may be one or more of the halogen anions of chlorine (Cl), bromine (Br), or iodine (I).

[0115] According to an embodiment, Y' may be an anion having an oxidation number of -1. Y' is different from X. For example, Y' may be one or more of the following anions: SO3 - 、CH3COO -, CN - 、NO3 - 、NO2 - 、H2PO4 - PF6 - OH - 、BF4 - 、N(CF3SO2)2 - CF3CO2 - CF3SO3 - 、C(CF3SO2)3 - 、HCO3 - 、ClO4 - 、HSO4 - , or SCN - .

[0116] According to an embodiment, Z may be one or more of the following anions: (BO4) 3- 、(BO3) 3- 、(PO4) 3- , [Fe(CN)6] 3- , or [Ag(S2O3)2] 3- .

[0117] According to an embodiment, 0.5 ≤ a ≤ 7, or 0.5 ≤ a ≤ 6, or 1 ≤ a ≤ 5, or 1 ≤ a ≤ 4, or 1 ≤ a ≤ 3.

[0118] According to an embodiment, 0.5 ≤ b ≤ 2, 0.75 ≤ b ≤ 2, or 1 ≤ b ≤ 2.

[0119] Depending on the implementation, 0 < c ≤ 6, or 1 < c ≤ 6, or 3 < c ≤ 6.

[0120] Depending on the implementation, 0 ≤ d ≤ 6, 0.5 ≤ d ≤ 6, or 1 ≤ d ≤ 6.

[0121] Depending on the implementation, 0 ≤ e ≤ 6, 0.5 ≤ e ≤ 6, or 1 ≤ e ≤ 6.

[0122] Depending on the implementation, 0 < c + d + e ≤ 6, 0.5 < c + d + e ≤ 6, or 1 < c + d + e ≤ 6.

[0123] The compound of Formula 1 is a halide-based compound and includes X (halogen anions) having a large ionic radius, wherein one or three X (halogen anions) may be replaced by Y' (having an oxidation number of -1) anions and / or Z (having an oxidation number of -3) anions. The ionic conductivity of the hybrid solid-state ion conductor having the replaced anions may be maintained at the same level as or greater than that of the hybrid solid-state ion conductor having no replaced anions.

[0124] In one aspect, the salt of Formula 2 is located in the space surrounding the octahedral structure and is adjacent to the octahedral structure.

[0125] According to an embodiment, M" may be the same metal cation as M' in Formula 1, or a different metal cation having an ionic radius within ±10% of the ionic radius of M'. That is, M" may be one or more metal cations having an oxidation number of +2, +3, +4, +5, or +6, excluding alkali metal cations. For example, when the ionic radius of the metal cation of M' is 80 picometers, M" may be a metal cation having an ionic radius of 72 to 88 picometers, 74 to 86 picometers, or 76 to 84 picometers. The closer the metal cation radii of M' and M", the lower the activation energy of the hybrid solid-state ion conductor may be, thereby improving ionic conductivity.

[0126] The hybrid solid-state ion conductor according to an embodiment may include one or more pairs of: a Li2ZrCl6 compound and a Zr3(PO4)4 salt, a Li2ZrCl6 compound and a Zr3(PO4)4 salt, a LiTaCl6 compound and a Ta3(PO4)5 salt, a Li3YCl6 compound and a YPO4 salt, a Li3InCl6 compound and an In(PO4) salt, a Li3YBr6 compound and a YPO4 salt, a Li3ErCl6 compound and an Er(PO4) salt, a Li3ErI6 compound and an Er(PO4) salt, a Li3HoCl6 compound and a Ho(PO4) salt, a Li3TiCl6 compound and a Ti(PO4) salt Salts, Li2TiCl6 compounds and Ti3(PO4)4 salts, Li3YbCl6 compounds and Yb(PO4) salts, Li3LuCl6 compounds and Lu(PO4) salts, Li3TmCl6 compounds and Tm(PO4) salts, LiAlCl4 compounds and Al(PO4) salts, LiGaCl4 compounds and Ga(PO4) salts, LiVCl3 compounds and V3(PO4)2 salts, Li2HfCl6 compounds and Hf3(PO4)4 salts, Li3SmCl6 compounds and SmPO4 salts, LiNbCl6 compounds and Nb3(PO4)5 salts, or Li3LaCl6 compounds and LaPO4 salts.

[0127] The hybrid solid-state ion conductor according to an embodiment may have greater ion conductivity than a single halide-based solid-state ion conductor, and may have excellent charge and discharge characteristics.

[0128] According to an embodiment, impurities may not be included. In one aspect, the impurity may be the first component.

[0129] According to an embodiment, the impurity may be further included in an amount of greater than about 0 wt % and less than about 5 wt %, greater than about 0.1 wt % and less than about 4 wt %, greater than about 0.5 wt % and less than about 3 wt % based on 100 wt % of the total amount of the hybrid solid-state ion conductor. When the amount of the impurity is within this range, the chemical reactivity between the M' metal cation of the compound of Formula 1 and the metal cation included in the impurity is similar, so that the reduction in ionic conductivity may not be affected.

[0130] For example, the impurities may include a first component including one or more of the following: a compound represented by Formula 3, a salt represented by Formula 4, or a combination thereof:

[0131] Formula 3

[0132] (M1) p (X1) q (Y'1) r (Z1) s

[0133] in

[0134] M1 may be one or more metal cations having an oxidation number of +2, +3, +4, +5, or +6,

[0135] X1 can be one or more halogen anions,

[0136] Y'1 may be an anion having an oxidation number of -1,

[0137] Z1 may be an anion having an oxidation number of -3,

[0138] 0.5 ≤ p ≤ 2, 0 < q ≤ 6, 0 ≤ r ≤ 6, 0 ≤ s ≤ 6, and 0 < q + r + s ≤6.

[0139] Formula 4

[0140] (M2) t (PO4) v

[0141] in

[0142] M2 may be an alkali metal having an oxidation number of +1,

[0143] 0.5 ≤ t ≤ 7, and 0 < v ≤ 7 / 3.

[0144] For example, the impurities may include ZrCl4, ZrCl3, TaCl5, YCl3, ErCl3, or InCl3.

[0145] According to an embodiment, the compound of Formula 1 and the salt of Formula 2 may each be a nanoparticle having a particle size of about 1 nanometer (nm) to about 100 nm. For example, the compound of Formula 1 and the salt of Formula 2 may each be a nanoparticle having a particle size of about 1 nm to about 90 nm, about 1 nm to about 80 nm, about 1 nm to about 70 nm, about 1 nm to about 60 nm, or about 1 nm to about 50 nm, about 5 nm to about 100 nm, about 10 nm to about 80 nm, or about 15 nm to about 60 nm. In one aspect, particle size may refer to the diameter of the major axis of the particle. The particle size of multiple particles may be the average value (average size) of the particle size. The average size may be calculated as follows: the size of the particles is analyzed by scanning electron microscopy. The average value may be a mean or a median.

[0146] Figure 1A is a schematic diagram showing a crystal structure of a hybrid solid-state ion conductor according to an embodiment; Figure 1B is a schematic diagram showing a crystal structure of a hybrid solid-state ion conductor according to an embodiment. Figure 2 is a schematic diagram showing a unit cell in a crystal structure of a hybrid solid-state ion conductor according to an embodiment.

[0147] like Figure 1A , 1B , and 2, the hybrid solid-state ion conductor according to the embodiment has a distorted rock salt type crystal structure. The distorted rock salt type crystal structure herein may refer to a crystal structure that is similar to a rock salt structure, but has undergone a distortion or deviation from the ideal arrangement of the rock salt crystal structure. The rock salt crystal structure is a cubic close-packed arrangement of ions, in which each cation is surrounded by anions in a regular and repeated pattern, and vice versa. In the distorted rock salt structure, external factors such as temperature, pressure, or the presence of impurities may cause the lattice to deviate from the ideal cubic arrangement.

[0148] The compound of Formula 1 may have: an M'X6 octahedral structure, wherein an M' metal cation having an oxidation number of +2, +3, +4, +5, or +6 is located at the center of the crystal structure, and six X anions are located (coordinated) at its corners (X = one or more of the halogen elements), or M'X c Y' d Z eOctahedral structure, wherein some of the 6 anions located (coordinated) at its corners are replaced by one or more of the anions of Y' and Z (X = one or more of the halogen elements, Y' = anions with an oxidation number of -1, Z = anions with an oxidation number of -3, and c + d + e = 6). Adjacent octahedra share edges. In one aspect, the compound of Formula 1 has an octahedral structure as follows: wherein M' is a central metal cation coordinated by six halogen anions, wherein each halogen anion is optionally replaced by one or more of Y' or Z.

[0149] In the salt of formula 2, M" metal cation and (PO4) 3- The anion is located in the space around the octahedron together with M (alkali metal) such as Li metal cation. The Li metal cation may have a LiX ionic bond, depending on the distance between it and the X halogen anion. In some embodiments, in which the excess M "metal cation is combined with the excess (PO4) 3- In the case of mixed salts of anions, M'X and / or Li3(PO4) impurities may also be generated.

[0150] The hybrid solid-state ion conductor may have a layered crystal structure. The hybrid solid-state ion conductor has lithium ion movement channels that are three-dimensionally connected in the x-axis, y-axis, and z-axis directions in a three-dimensional region, and the salt of Formula 2 is a nano-sized particle and acts as a filler in the space around the compound of Formula 1. Therefore, it is believed that the ion conductivity of the hybrid solid-state ion conductor is improved and the charge and discharge characteristics are improved.

[0151] According to an embodiment, the amount of the salt of Formula 2 may be about 5 wt % to about 30 wt %, about 8 wt % to about 25 wt %, or about 10 wt % to about 20 wt %, based on 100 wt % of the total weight of the hybrid solid-state ion conductor. When the amount of the salt of Formula 2 is within this range, ionic conductivity and charge and discharge characteristics may be further improved.

[0152] According to an embodiment, in X-ray diffraction analysis using Cu Kα radiation, a main peak appears at a position where a diffraction angle 2θ is about 15°2θ to about 25°2θ, about 17°2θ to about 23°2θ, or about 19°2θ to about 21°2θ, and a secondary peak appears at a position where a diffraction angle 2θ is about 25°2θ to about 35°2θ, about 27°2θ to about 33°2θ, or about 29°2θ to about 31°2θ. In this regard, the main peak refers to a peak having a maximum intensity, and the secondary peak refers to a peak having a smaller intensity than the main peak.

[0153] According to an embodiment, the hybrid solid-state ion conductor may have a conductivity of about 8.0 x 10 -4 Siemens / cm (S cm -1) to about 3.0 x 10 -3 S cm -1 , about 9.0 x 10 -4 S cm -1 to about 3.0 x 10 -3 S cm -1 , or about 1.0 x10 -3 S cm -1 to about 3.0 x 10 -3 S cm -1 ion conductivity.

[0154] According to an embodiment, the hybrid solid-state ion conductor may have an activation energy of about 0.1 electron volts (eV) to about 0.35 eV, about 0.15 eV to about 0.3 eV, or about 0.2 eV to about 0.25 eV at 25°C.

[0155] Solid-state electrolytes, cathodes, and electrochemical devices

[0156] According to further embodiments, the solid electrolyte may include the hybrid solid ion conductor as described above. The solid electrolyte including the hybrid solid ion conductor may provide an electrochemical device having improved ion conductivity and improved charge and discharge characteristics.

[0157] The solid electrolyte may be in a powder or molded form. The molded product of the solid electrolyte may have the form of a disc, a sheet, a film, etc. For example, the solid electrolyte may be in the form of a disc. However, the molded product of the solid electrolyte is not limited thereto and may be manufactured in different forms depending on the purpose.

[0158] According to further embodiments, the positive electrode may include a hybrid solid-state ion conductor as described above.

[0159] According to another embodiment, the electrochemical device may include a solid electrolyte as described above in at least one of a positive electrode layer, a negative electrode layer, and a solid electrolyte layer. In one aspect, the electrochemical device includes: a positive electrode layer; a negative electrode layer; and a solid electrolyte layer between the positive electrode layer and the negative electrode layer, wherein the solid electrolyte is in at least one of the positive electrode layer, the negative electrode layer, or the solid electrolyte layer.

[0160] The electrochemical device according to the embodiment may be an electrochemical cell, a storage battery, a supercapacitor, a fuel cell, a sensor, or a color changing device. For example, the electrochemical device may be an electrochemical cell. For example, the electrochemical cell may be an all-solid-state secondary battery.

[0161] Figures 3 to 5 is a cross-sectional view of an all-solid-state secondary battery 1 or 1 a according to an embodiment.

[0162] exist Figures 3 to 5 In the embodiment, the all-solid-state secondary battery 1 or 1a includes: a positive electrode layer 10 including a positive electrode current collector 11 and a positive electrode active material layer 12, a negative electrode layer 20, and a solid electrolyte layer 30 disposed between the positive electrode layer 10 and the negative electrode layer 20. The negative electrode layer 20 includes a negative electrode current collector 21 and a negative electrode active material layer 22 disposed on the negative electrode current collector 21, wherein the negative electrode active material layer 22 may include lithium metal or a negative electrode active material that forms an alloy with lithium. One or more of the positive electrode layer 10, the negative electrode layer 20, or the solid electrolyte layer 30 of the all-solid-state secondary battery 1 or 1a may include a solid ion conductor as described above.

[0163] The positive electrode layer 10 according to the embodiment may include the mixed solid ion conductor as described above, and the solid electrolyte layer 30 may include a solid electrolyte of a sulfide-based solid electrolyte, an oxide-based solid electrolyte, a polymer solid electrolyte, or a combination thereof.

[0164] The positive electrode layer 10 according to the embodiment includes the mixed solid-state ion conductor as described above, and in addition to the mixed solid-state ion conductor as described above, the solid electrolyte layer 30 may further include the following different solid electrolytes: a sulfide-based solid electrolyte, an oxide-based solid electrolyte, a polymer solid electrolyte, or a combination thereof. In one aspect, the positive electrode layer includes the solid electrolyte, and the solid electrolyte layer includes: a first solid electrolyte including the solid electrolyte, and a second solid electrolyte including a sulfide-containing solid electrolyte, an oxide-containing solid electrolyte, a polymer solid electrolyte, or a combination thereof.

[0165] A metal substrate may be used as the positive electrode current collector 11. Examples of the metal substrate include a plate or foil including indium (In), copper (Cu), magnesium (Mg), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), zinc (Zn), aluminum (Al), germanium (Ge), lithium (Li), alloys thereof, or combinations thereof. The positive electrode current collector 11 may be omitted.

[0166] The positive electrode active material layer 12 is a layer obtained from a composition including a positive electrode active material and a solid electrolyte. The solid electrolyte included in the positive electrode layer 10 may be the same as or different from the solid electrolyte included in the solid electrolyte layer 30. For example, the positive electrode active material layer 12 may include a solid electrolyte including a mixed solid ion conductor as described above.

[0167] The positive electrode active material may be used without limitation as long as it can be suitably used in the all-solid-state secondary batteries 1 and 1a. For example, as the positive electrode active material, one or more composite oxides of lithium and the following metals may be used: cobalt, manganese, nickel, or a combination thereof. Examples thereof include Li aA 1-b B' b D'2 (where 0.90 ≤ a ≤ 1.8 and 0 ≤ b ≤ 0.5); Li a E 1-b B' b O 2-c D' c (where 0.90 ≤ a ≤ 1.8, 0 ≤ b ≤ 0.5, and 0 ≤ c ≤ 0.05); LiE 2-b B' b O 4-c D' c (where 0 ≤ b ≤ 0.5 and 0 ≤ c ≤ 0.05); Li a Ni 1-b-c Co b B' c D' α (where 0.90 ≤ a ≤1.8, 0 ≤ b ≤ 0.5, 0 ≤ c ≤ 0.05, and 0 < α ≤ 2); Li a Ni 1-b-c Co b B' c O 2-α F' α (where 0.90≤ a ≤ 1.8, 0 ≤ b ≤ 0.5, 0 ≤ c ≤ 0.05, and 0 < α < 2); Li a Ni 1-b-c Co b B' c O 2-α F'2 (where 0.90 ≤ a ≤ 1.8, 0 ≤ b ≤ 0.5, 0 ≤ c ≤ 0.05, and 0 < α < 2); Li a Ni 1-b-c Mn b B' c D' α (where 0.90 ≤ a ≤ 1.8, 0 ≤ b ≤ 0.5, 0 ≤ c ≤ 0.05, and 0 < α ≤ 2); Li a Ni 1-b- c Mn b B' c O 2-α F' α (where 0.90 ≤ a ≤ 1.8, 0 ≤ b ≤ 0.5, 0 ≤ c ≤ 0.05, and 0 < α < 2); Li a Ni 1-b-c Mnb B' c O 2-α F'2 (where 0.90 ≤ a ≤ 1.8, 0 ≤ b ≤ 0.5, 0 ≤ c ≤ 0.05, and 0 < α< 2); Li a Ni b E c G d O2 (where 0.90 ≤ a ≤ 1.8, 0 ≤ b ≤ 0.9, 0 ≤ c ≤ 0.5, and 0.001 ≤ d≤ 0.1); Li a Ni b Co c Mn d G e O2 (where 0.90 ≤ a ≤ 1.8, 0 ≤ b ≤ 0.9, 0 ≤ c ≤ 0.5, 0 ≤ d ≤ 0.5, and 0.001 ≤ e ≤ 0.1); Li a NeG b O2 (where 0.90 ≤ a ≤ 1.8 and 0.001 ≤ b ≤0.1); Li a CoG b O2 (where 0.90 ≤ a ≤ 1.8 and 0.001 ≤ b ≤ 0.1); Li a MnG b O2 (where 0.90 ≤ a ≤ 1.8 and 0.001 ≤ b ≤ 0.1); Li a Mn b O4 (where 0.90 ≤ a ≤ 1.8 and 0.001 ≤ b ≤0.1); QO2; QS2; LiQS2; V2O5; LiV2O2; LiI'O2; LiNiVO4; Li (3-f) J2(PO4)3(0 ≤ f ≤ 2);Li (3-f)Fe2(PO4)3(0 ≤ f ≤ 2); LiFePO4, or a combination thereof. With respect to these formulas, A may be Ni, Co, Mn, or a combination thereof; B' may be Al, Ni, Co, Mn, Cr, Fe, Mg, Sr, V, a rare earth element, or a combination thereof; D' may be O, F, S, P, or a combination thereof; E may be Co, Mn, or a combination thereof; F' may be F, S, P, or a combination thereof; G may be Al, Cr, Mn, Fe, Mg, La, Ce, Sr, V, or a combination thereof; Q may be Ti, Mo, Mn, or a combination thereof; I' may be Cr, V, Fe, Sc, Y, or a combination thereof; and J may be V, Cr, Mn, Co, Ni, Cu, or a combination thereof. For example, the positive electrode active material includes one or more of the following: lithium cobalt oxide, lithium nickel oxide, lithium nickel cobalt oxide, lithium nickel cobalt aluminum oxide, lithium nickel cobalt manganese oxide, lithium manganese oxide, lithium iron phosphate, nickel sulfide, copper sulfide, lithium sulfide, iron oxide, or vanadium oxide. For example, the positive electrode active material may be LiCoO2, LiMn x O 2x (x=1, 2), LiNi 1-x Mn x O2(0 <x<1)、LiNi 1-x-y Co x Mn y O2 (0≤x≤0.5, 0≤y≤0.5), LiFePO4, TiS2, FeS2, TiS3, FeS3, etc.

[0168] The positive electrode active material layer 12 may further include an ionic liquid electrolyte. The ionic liquid electrolyte may be non-volatile. An ionic liquid refers to a salt in a liquid state at room temperature or a molten salt at room temperature, which has a melting point below room temperature and is composed only of ions. The ionic liquid may be one of the following compounds: a) one or more cations: ammonium-based cations, pyrrolidine-based cations, Cations based on pyridine Cationic, pyrimidine-based Cation, imidazole-based Cation, based on piperidine Cations based on pyrazole Cations, based on Azoles Cationic, pyridazine-based Cations, based on cations based on sulfonium, cations based on triazole cations, or mixtures thereof; and b) one or more of the following anions: BF4 - PF6 - 、AsF6 - 、SbF6- 、AlCl4 - 、HSO4 - 、ClO4 - 、CH3SO3 - CF3CO2 - , Cl - Br - ,I - 、SO4 2- CF3SO3 - 、(FSO2)2N - 、(C2F5SO2)2N - 、(C2F5SO2)(CF3SO2)N - , or (CF3SO2)2N - For example, the ionic liquid may include one or more of the following: bis(trifluoromethanesulfonyl)imide N-methyl-N-propylpyrrolidine , bis(trifluoromethanesulfonyl)imide N-butyl-N-methylpyrrolidine , bis(trifluoromethanesulfonyl)imide 1-butyl-3-methylimidazole , or bis(trifluoromethanesulfonyl)imide 1-ethyl-3-methylimidazole The polymeric ionic liquid may include repeating units comprising: a) one or more cations as follows: ammonium-based cations, pyrrolidine-based cations Cations based on pyridine Cationic, pyrimidine-based Cation, imidazole-based Cation, based on piperidine Cations based on pyrazole Cations, based on Azoles Cationic, pyridazine-based Cations, based on cations based on sulfonium, cations based on triazole cations, or mixtures thereof; and b) one or more anions as follows: BF4 - PF6 - 、AsF6 - 、SbF6 - 、AlCl4 - 、HSO4 - 、ClO4 - 、CH3SO3 - CF3CO2 - 、(CF3SO2)2N - 、(FSO2)2N - , Cl - Br- ,I - 、SO4 2- CF3SO3 - 、(C2F5SO2)2N - 、(C2F5SO2)(CF3SO2)N - 、NO3 - 、Al2Cl7 - 、(CF3SO2)3C - 、(CF3)2PF4 - 、(CF3)3PF3 - 、(CF3)4PF2 - 、(CF3)5PF - 、(CF3)6P - 、SF5CF2SO3 - 、SF5CHFCF2SO3 - CF3CF2(CF3)2CO - 、(CF3SO2)2CH - 、(SF5)3C - , or (O(CF3)2C2(CF3)2O)2PO - .

[0169] The ionic liquid electrolyte may fill the pores of the surface of the positive electrode active material layer 12 in contact with the solid electrolyte layer 30. The amount of the ionic liquid electrolyte may be about 0.1 parts by weight to about 20 parts by weight, about 0.1 parts by weight to about 15 parts by weight, about 0.1 parts by weight to about 10 parts by weight, or about 0.1 parts by weight to about 5 parts by weight, based on 100 parts by weight of the positive electrode active material layer 12 not including the ionic liquid electrolyte. By improving ionic conductivity due to the inclusion of the ionic liquid electrolyte, the charge and discharge characteristics of the all-solid-state secondary batteries 1 and 1a may be improved.

[0170] The positive electrode active material layer 12 may further include a conductive material or a binder. For example, the conductive material may include carbon black, carbon fiber, graphite, or a combination thereof. For example, the carbon black may be acetylene black, Ketjen black, Super P carbon, channel black, furnace black, lamp black, pyrolytic carbon black, or a combination thereof. Graphite may be natural graphite or artificial graphite. A combination of at least two of the foregoing materials may be used. In addition to the conductive materials described above, the positive electrode active material layer 12 may additionally include conductive materials of different compositions. Additional conductive materials include conductive fibers such as metal fibers; fluorocarbon powders; metal powders such as aluminum powders or nickel powders; conductive whiskers such as zinc oxide or potassium titanate; polyethylene derivatives; or combinations thereof. The amount of the conductive material may be in the range of about 1 part by weight to about 10 parts by weight, for example, about 2 parts by weight to about 7 parts by weight, based on 100 parts by weight of the positive electrode active material. When the amount of the conductive material is within this range, for example, about 1 part by weight to about 10 parts by weight, the conductivity of the positive electrode layer 10 may be sufficient (appropriate).

[0171] The binder can improve adhesion between components of the positive electrode layer 10 and adhesion to the positive electrode current collector 11. Examples of binders include polyacrylic acid (PAA), polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene rubber (EPDM), sulfonated EPDM, styrene-butadiene rubber, fluorinated rubber, copolymers thereof, or combinations thereof. The amount of the binder may be in the range of about 1 part by weight to about 10 parts by weight, for example, in the range of about 2 parts by weight to about 7 parts by weight, based on 100 parts by weight of the positive electrode active material. When the amount of the binder is within this range, the adhesion of the positive electrode active material layer 12 to the positive electrode current collector 11 is further improved, and the reduction in the energy density of the positive electrode active material layer 12 can be suppressed.

[0172] Solvents such as N-methylpyrrolidone, acetone, and water may be used. The amounts of the positive electrode active material, conductive material, binder, and solvent are at levels suitably used in an all-solid-state secondary battery.

[0173] The positive electrode active material layer 12 can be prepared by appropriately mixing additives such as fillers, dispersants, and ion conduction aids in addition to the positive electrode active material, solid electrolyte, conductive material, and binder as described above. If necessary, a plasticizer can be added to the composition to form pores in the positive electrode active material layer 12. As fillers, dispersants, ion conduction aids, plasticizers, etc., known materials commonly used in electrodes of all-solid-state secondary batteries 1 and 1a can be used.

[0174] The negative electrode layer 20 may include a negative electrode current collector 21 and a negative electrode active material layer 22 .

[0175] The material constituting the negative electrode current collector 21 includes copper (Cu), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), or nickel (Ni). The negative electrode current collector 21 may include one type of metal, or an alloy or coating material of two or more metals. The negative electrode current collector 21 may be formed, for example, in a plate shape or a foil shape.

[0176] The negative electrode active material layer 22 may include lithium metal or a lithium alloy. Examples of lithium alloys may include lithium and one or more of gold, platinum, palladium, silver, aluminum, bismuth, tin, or zinc. If necessary, the negative electrode active material layer 22 may include a carbon-based (i.e., carbon-containing) negative electrode active material, or a negative electrode active material including a combination of lithium metal or a lithium alloy and a carbon-based negative electrode active material.

[0177] The carbon-based negative active material includes graphite, carbon black (CB), acetylene black (AB), furnace black (FB), Ketjen black (KB), graphene, carbon nanotubes, or carbon nanofibers.

[0178] The negative electrode active material layer 22 can be formed by appropriately mixing additives such as a conductive material, a binder, a filler, a dispersant, and an ion-conducting aid, which include the same materials as those described in the positive electrode layer 10 .

[0179] If necessary, the negative electrode active material layer 22 may be a negative electrode-free coating. For example, the negative electrode-free coating may contain metals such as silicon and carbon, and may have a structure in which a conductive binder is disposed around the metal and carbon. The thickness of the negative electrode-free coating may be 1 μm to 20 μm.

[0180] The solid electrolyte layer 30 may include a mixed solid ion conductor as described above.

[0181] The solid electrolyte layer 30 may further include an oxide-based solid electrolyte, a sulfide-based solid electrolyte, a polymer solid electrolyte, or a combination thereof.

[0182] In one aspect, the solid electrolyte layer 30 includes: a first solid electrolyte including the solid electrolyte, and a second solid electrolyte including a sulfide-containing solid electrolyte, an oxide-containing solid electrolyte, a polymer solid electrolyte, or a combination thereof.

[0183] In one aspect, the positive electrode layer includes the solid electrolyte, and the solid electrolyte layer 30 includes: a first solid electrolyte including the solid electrolyte, and a second solid electrolyte including a sulfide-containing solid electrolyte, an oxide-containing solid electrolyte, a polymer solid electrolyte, or a combination thereof.

[0184] The solid electrolyte layer 30 may be a single layer or a multilayer of two or more layers. For example, the solid electrolyte layer 30 may be a double-layer solid electrolyte layer, which includes a first solid electrolyte layer placed in contact with the positive electrode layer 10 and a second solid electrolyte layer on the first solid electrolyte layer. The first solid electrolyte layer may be a mixed solid ion conductor as described above, and the second solid electrolyte layer may be an oxide-based solid electrolyte, a sulfide-based solid electrolyte, a polymer solid electrolyte, or a combination thereof. In some embodiments, the first solid electrolyte layer may be an oxide-based solid electrolyte, a sulfide-based solid electrolyte, a polymer solid electrolyte, or a combination thereof, and the second solid electrolyte layer may be a mixed solid ion conductor as described above.

[0185] Examples of oxide-based solid electrolytes may include one or more of the following: Li 1+x+y Al x Ti 2-x Si y P 3- y O 12 (0 <x<2,0≤y<3),BaTiO3,Pb(Zr,Ti)O3(PZT),Pb 1-x La x Zr 1-y Ti y O3(PLZT) (0≤x<1, 0≤y<1), Pb(Mg 1 / 3 Nb 2 / 3 )O3-PbTiO3 (PMN-PT), HfO2, SrTiO3, SnO2, CeO2, Na2O, MgO, NiO, CaO, BaO, ZnO, ZrO2, Y2O3, Al2O3, TiO2, SiO2, Li3PO4, Li x Ti y (PO4)3(0 <x<2,0<y<3),Li x Al y Ti z (PO4)3 (0 <x<2,0<y<1,0<z<3),Li 1+x+y (Al,Ga) x (Ti, Ge) 2-x Si y P 3-y O 12 (0≤x≤1,0≤y≤1), Li x La yTiO3(0 < x < 2, 0 < y < 3), Li2O, LiOH, Li2CO3, LiAlO2, Li2O - Al2O3 - SiO2 - P2O5 - TiO2 - GeO2, or Li 3+ x La3M2O 12 (M = Te, Nb, or Zr, where x is an integer from 1 - 10).

[0186] The oxide - based solid electrolyte can be prepared by a sintering method, a casting (flow - casting) method, etc.

[0187] For example, the oxide - based solid electrolyte can be a garnet - based solid electrolyte.

[0188] For example, the garnet - based solid electrolyte (e.g., an electrolyte isostructural with garnet) can include an oxide represented by Formula 5

[0189] Formula 5

[0190] (Li x M'1 y )(M'2) 3-δ (M'3) 2-ω O 12-z X' z

[0191] where in the formula, 6 ≤ x ≤ 8, 0 ≤ y < 2, - 0.2 ≤ δ ≤ 0.2, - 0.2 ≤ ω ≤ 0.2, and 0 ≤ z ≤ 2

[0192] M'1 can be a monovalent cation, a divalent cation, a trivalent cation, or a combination thereof

[0193] M'2 can be a monovalent cation, a divalent cation, a trivalent cation, or a combination thereof

[0194] M'3 can be a monovalent cation, a divalent cation, a trivalent cation, a tetravalent cation, a pentavalent cation, a hexavalent cation, or a combination thereof

[0195] X' can be a monovalent anion, a divalent anion, a trivalent anion, or a combination thereof

[0196] In Formula 5, examples of monovalent cations include Na, K, Rb, Cs, H, Fr, etc., and examples of divalent cations include Mg, Ca, Ba, Sr, etc. Examples of trivalent cations are In, Sc, Cr, Au, B, Al, and Ga, and examples of tetravalent cations in Formula 5 are Sn, Ti, Mn, Ir, Ru, Pd, Mo, Hf, Ge, V, and Si. Examples of pentavalent cations are Nb, Ta, Sb, V, and P.

[0197] M′1 may be, for example, hydrogen (H), iron (Fe), gallium (Ga), aluminum (Al), boron (B), beryllium (Be), or a combination thereof. M'2 may be lanthanum (La), barium (Ba), calcium (Ca), strontium (Sr), yttrium (Y), bismuth (Bi), praseodymium (Pr), neodymium (Nd), actinium (Ac), samarium (Sm), gadolinium (Gd), or a combination thereof, and M'3 may be zirconium (Zr), hafnium (Hf), tin (Sn), niobium (Nb), titanium (Ti), vanadium (V), chromium (Cr), manganese (Mn), cobalt (Co), nickel (Ni), copper (Cu), molybdenum (Mo), tungsten (W), tantalum (Ta), magnesium (Mg), technetium (Tc), ruthenium (Ru), palladium (Pd), iridium (Ir), scandium (Sc), cadmium (Cd), indium (In), antimony (Sb), tellurium (Te), thallium (Tl), platinum (Pt), silicon (Si), aluminum (Al), or a combination thereof.

[0198] Regarding Formula 5, the monovalent anion used as X' may be a halogen atom, a pseudohalogen, or a combination thereof, and the divalent anion may be S 2- or Se 2- , and the trivalent anion may be, for example, N 3- .

[0199] In Formula 5, 6.6≤x≤8, 6.7≤x≤7.5, or 6.8≤x≤7.1.

[0200] For example, the garnet-based solid electrolyte may include an oxide represented by Formula 6,

[0201] Formula 6

[0202] (Li x M'1 y )(La a1 M'2 a2 ) 3-δ (Zr b1 M'3 b2 ) 2-ω O 12-z X' z

[0203] Wherein in the formula, M'1 can be hydrogen (H), iron (Fe), gallium (Ga), aluminum (Al), boron (B), beryllium (Be), or a combination thereof,

[0204] M'2 may be barium (Ba), calcium (Ca), strontium (Sr), yttrium (Y), bismuth (Bi), praseodymium (Pr), neodymium (Nd), actinium (Ac), samarium (Sm), gadolinium (Gd), or a combination thereof,

[0205] M'3 can be hafnium (Hf), tin (Sn), niobium (Nb), titanium (Ti), vanadium (V), chromium (Cr), manganese (Mn), cobalt (Co), nickel (Ni), copper (Cu), molybdenum (Mo), tungsten (W), tantalum (Ta), magnesium (Mg), technetium (Tc), ruthenium (Ru), palladium (Pd), iridium (Ir), scandium (Sc), cadmium (Cd), indium (In), antimony (Sb), tellurium (Te), thallium (Tl), platinum (Pt), silicon (Si), aluminum (Al), or a combination thereof,

[0206] 6 ≤ x ≤ 8, 0 ≤ y < 2, -0.2 ≤ δ ≤ 0.2, -0.2 ≤ ω ≤ 0.2, 0 ≤ z ≤ 2,

[0207] a1 + a2 = 1, 0 < a1 ≤ 1, 0 ≤ a2 < 1,

[0208] b1 + b2 = 1, 0 < b1 ≤ 1, 0 ≤ b2 < 1, and

[0209] X' can be a monovalent anion, a divalent anion, a trivalent anion, or a combination thereof.

[0210] Regarding Formula 6, the monovalent anion used as X' can be a halogen atom, a pseudohalogen, or a combination thereof, and the divalent anion can be S 2- or Se 2- , and the trivalent anion can be, for example, N 3- .

[0211] In Formula 6, 6.6 ≤ x ≤ 8, 6.7 ≤ x ≤ 7.5, or 6.8 ≤ x ≤ 7.1.

[0212] The term "pseudohalogen" used herein is a molecule composed of two or more electronegative atoms that is similar to a halogen in the free state and can produce an anion similar to a halide ion. Examples of pseudohalogens are cyanide, cyanate, thiocyanate, azide, or a combination thereof.

[0213] The halogen atom can be, for example, iodine (I), chlorine (Cl), bromine (Br), fluorine (F), or a combination thereof, and the pseudohalogen can be, for example, cyanide, cyanate, thiocyanate, azide, or a combination thereof.

[0214] The trivalent anion can be, for example, N 3- .

[0215] According to another embodiment, the garnet-based solid electrolyte can be an oxide represented by Formula 7,

[0216] Formula 7

[0217] Li 3+x La3Zr 2-a (M'4) a O12

[0218] Wherein M'4 in Formula 7 may be Al, Ga, In, Si, Ge, Sn, Sb, Bi, Sc, Y, Ti, Hf, V, Nb, Ta, W, or a combination thereof, and x may be a number of 1-10, and 0≤a<2.

[0219] An example of a garnet-based solid electrolyte is Li7La3Zr2O 12 and Li 6.5 Ln3Z 1.5 Ta 0.5 O 12 .

[0220] The garnet-based solid electrolyte can have a conductivity of 1 mS·cm -1 The garnet-based solid electrolyte can be prepared in a wide temperature range to have a variety of thicknesses.

[0221] The sulfide-based solid electrolyte is not particularly limited as long as it includes sulfur (S) or a sulfur-based element (Se, Te) and has ion conductivity. For example, the sulfide-based solid electrolyte may include one or more of the following: Li2S-P2S5, Li2S-P2S5-LiX (wherein X is a halogen element), Li2S-P2S5-Li2O, Li2S-P2S5-Li2O-LiI, Li2S-SiS2, Li2S-SiS2-LiI, Li2S-SiS2-LiBr, Li2S-SiS2-LiCl, Li2S-SiS2-B2S3-LiI, Li2S-SiS2-P2S5-LiI, Li2S-B2S3, Li2S-P2S5-Z m S n (m and n are positive numbers, and Z is one of Ge, Zn, or Ga), Li2S-GeS2, Li2S-SiS2-Li3PO4, or Li2S-SiS2-Li p MO q (p and q are positive numbers, and M may be one of P, Si, Ge, B, Al, Ga, and In). When the sulfide-based solid electrolyte material includes Li2S-P2S5, the mixing molar ratio of Li2S and P2S5 may be selected in the range of 50:50 to 90:10, may be selected in the range of 60:40 to 90:10, or may be selected in the range of 75:25 to 90:10. The sulfide-based solid electrolyte may be prepared by treating the starting raw materials (e.g., Li2S, P2S5, etc.) by a melt quenching method, a mechanical grinding method, or the like. In some embodiments, calcination may be performed after the treatment.

[0222] The sulfide-based solid electrolyte may include a compound represented by Formula 8,

[0223] Formula 8

[0224] Li a M'5 x PS y M'6 z M'7 w

[0225] wherein in Formula 8, M'5 may be one or more metal elements other than Li in Groups 1 to 15 of the periodic table, and M'6 may be one or more elements in Group 17 of the periodic table, and

[0226] M'7 may be SO n , 4 ≤ a ≤ 8, 0 ≤ x < 1, 3 ≤ y ≤ 7, 0 < z ≤ 5, 0 ≤ w < 2, and 1.5 ≤ n ≤ 5.

[0227] In Formula 8, 0 < z ≤ 5, 0 < z ≤ 4, 0 < z ≤ 3, 0 < z ≤ 2, 0.2 ≤ z ≤ 1.8, 0.5 ≤ z ≤ 1.8, 1.0 ≤ z ≤ 1.8 or 1.0 ≤ z ≤ 1.5.

[0228] Regarding Formula 8, 5 ≤ a ≤ 8, 0 ≤ x ≤ 0.7, 4 ≤ y ≤ 7, 0 < z ≤ 2, and 0 ≤ w ≤ 0.5. For example, 5 ≤ a ≤ 7, 0 ≤ x ≤ 0.5, 4 ≤ y ≤ 6, 0 < z ≤ 2, and 0 ≤ w ≤ 0.2. For example, 5.5 ≤ a ≤ 7, 0 ≤ x ≤ 0.3, 4.5 ≤ y ≤ 6, 0.2 ≤ z ≤ 1.8, and 0 ≤ w ≤ 0.1. For example, 5.5 ≤ a ≤ 6, 0 ≤ x ≤ 0.05, 4.5 ≤ y ≤ 5, 1.0 ≤ z ≤ 1.5, and 0 ≤ w ≤ 0.1.

[0229] Regarding the compound represented by Formula 8, for example, M'5 may include Na, K, Mg, Ag, Cu, Hf, In, Ti, Pb, Sb, Fe, Zr, Zn, Cr, B, Sn, Ge, Si, Zr, Ta, Nb, V, Ga, Al, As, or a combination thereof. M'5 may be, for example, a monovalent cation or a divalent cation.

[0230] Regarding the compound represented by Formula 8, for example, M'6 may include F, Cl, Br, I, or a combination thereof. M'6 may be, for example, a monovalent anion.

[0231] Regarding the compound represented by Formula 8, for example, SO of M'7 n may be S4O6, S3O6, S2O3, S2O4, S2O5, S2O6, S2O7, S2O8, SO4, SO5, or a combination thereof. SO nmay be, for example, a divalent anion. SO n 2- may be, for example, S4O6 2- , S3O6 2- , S2O3 2- , S2O4 2- , S2O5 2- , S2O6 2- , S2O7 2- , S2O8 2- , SO4 2- , SO5 2- , or a combination thereof.

[0232] For example, the compound represented by Formula 8 may be a compound selected from the compounds represented by Formulas 8a to 8b:

[0233] Formula 8a

[0234] Li a PS y M"7 z M'8 w

[0235] wherein in Formula 8a, M"7 may be one or more elements of Group 17 of the periodic table, M'8 may be SO n , and 4 ≤ a ≤ 8, 3 ≤ y ≤ 7, 0 < z ≤ 5, 0 < w < 2, and 1.5 ≤ n ≤ 5,

[0236] Formula 8b

[0237] Li a M'9 x PS y M'10 z M'11 w

[0238] wherein in Formula 8b, M'9 may be one or more metal elements other than Li of Groups 1 to 15 of the periodic table, and M'10 may be one or more elements of Group 17 of the periodic table, and

[0239] M'11 may be SO n , 4 ≤ a ≤ 8, 0 < x < 1, 3 ≤ y ≤ 7, 0 < z ≤ 5, 0 < w < 2, and 1.5 ≤ n ≤ 5.

[0240] Regarding Formulas 8a and 8b, 0 < z ≤ 5, 0 < z ≤ 4, 0 < z ≤ 3, 0 < z ≤ 2, 0.2 ≤ z ≤ 1.8, 0.5 ≤ z ≤ 1.8, 1.0 ≤ z ≤ 1.8 or 1.0 ≤ z ≤ 1.5. Regarding Formulas 8a and 8b, for example, 5 ≤ a ≤ 8, 4 ≤ y ≤ 7, 0 < z ≤ 2, and 0 ≤ w ≤ 0.5; 5.5 ≤ a ≤ 7, 4.5 ≤ y ≤ 6, 0.2 ≤ z ≤ 1.8, and 0 ≤ w ≤ 0.1; 0.5 ≤ z ≤ 1.8; or 1.0 ≤ z ≤ 1.8.

[0241] For example, the compound represented by Formula 8 may be the compound represented by Formula 9,

[0242] Formula 9

[0243] Li 7-m×v-z M'12 v PS 6-z M'13 z1 M'14 z2

[0244] wherein M'12 may be Na, K, Mg, Ag, Cu, Hf, In, Ti, Pb, Sb, Fe, Zr, Zn, Cr, B, Sn, Ge, Si, Zr, Ta, Nb, V, Ga, Al, As, or a combination thereof, m may be the oxidation number of M'12, M'13 and M'14 may each independently be F, Cl, Br, or I, and 0 < v ≤ 0.7, 0 < z1 < 2, 0 ≤ z2 < 1, 0 < z < 2, z = z1 + z2, and 1 ≤ m ≤ 2.

[0245] For example, 0 < v ≤ 0.7, 0 < z1 < 2, 0 ≤ z2 ≤ 0.5, 0 < z < 2, and z = z1 + z2. For example, 0 < v ≤ 0.5, 0 < z1 < 2, 0 ≤ z2 ≤ 0.5, 0 < z < 2, and z = z1 + z2. For example, 0 < v ≤ 0.3, 0 < z1 ≤ 1.5, 0 ≤ z2 ≤ 0.5, 0.2 ≤ z ≤ 1.8, and z = z1 + z2. For example, 0 < v ≤ 0.1, 0 < z1 ≤ 1.5, 0 ≤ z2 ≤ 0.5, 0.5 ≤ z ≤ 1.8, and z = z1 + z2. For example, 0 < v ≤ 0.05, 0 < z1 ≤ 1.5, 0 ≤ z2 ≤ 0.2, 1.0 ≤ z ≤ 1.8, and z = z1 + z2. M'12 may be, for example, one metal element or two metal elements.

[0246] For example, the compound represented by Formula 9 may contain one type of halogen element or two types of halogen elements.

[0247] For example, the compound represented by Formula 9 may be a solid-state ionic conductor compound represented by Formulas 9a to 9f:

[0248] Formula 9a

[0249] Li 7-z PS 6-z M'15 z1 M'16 z2

[0250] Formula 9b

[0251] Li 7-v-z Na v PS 6-z M'15 z1 M'16 z2

[0252] Formula 9c

[0253] Li 7-v-z K v PS 6-z M'15 z1 M'16 z2

[0254] Formula 9d

[0255] Li 7-v-z Cu v PS 6-z M'15 z1 M'16 z2

[0256] Formula 9e

[0257] Li 7-2v-z Mg v PS 6-z M'15 z1 M'16 z2

[0258] Formula 9f

[0259] Li 7-v-z Ag v PS 6-z M'15 z1 M'16 z2

[0260] Wherein in these formulas, M'15 and M'16 can each independently be F, Cl, Br, or I,

[0261] 0 < v ≤ 0.7, 0 < z < 2, 0 ≤ z1 < 1, 0 < z2 < 2, and z = z1 + z2.

[0262] Regarding Formulas 9a to 9f, the following conditions can each be independently satisfied: for example, 0 < v ≤ 0.7, 0 < z1 < 2, 0 ≤ z2 ≤ 0.5, 0 < z < 2, and z = z1 + z2; 0 < v ≤ 0.5, 0 < z1 < 2, 0 ≤ z2 ≤ 0.5, 0 < z < 2, and z = z1 + z2; 0 < v ≤ 0.3, 0 < z1 ≤ 1.5, 0 ≤ z2 ≤ 0.5, 0.2 ≤ z ≤ 1.8, and z = z1 + z2; 0 < v ≤ 0.05, 0 < z1 ≤ 1.5, 0 ≤ z2 ≤ 0.2, 1.0 ≤ z ≤ 1.8, and z = z1 + z2, for example, 0 < v ≤ 0.05, 0 < z1 ≤ 1.5, 0 ≤ z2 ≤ 0.2, 1.0 ≤ z ≤ 1.5, and z = z1 + z2. In Formula 9a, v = 0.

[0263] The compound represented by Formula 8 can be, for example, a compound represented by one of the following formulas:

[0264] Li 7-z PS 6-z F z1 , Li 7-z PS 6-z Cl z1 , Li 7-z PS 6-z Br z1 , Li 7-z PS 6-z I z1 , Li 7-z PS 6-z F z1 Cl z2 , Li 7- z PS 6-z F z1 Br z2 , Li 7-z PS 6-z F z1 I z2 , Li 7-z PS 6-z Cl z1 Br z2 , Li 7-z PS 6-z Cl z1 I z2 , Li 7-z PS 6-z Cl z1 F z2 , Li 7- z PS 6-z Br z1 I z2 , Li 7-z PS 6-z Br z1F z2 ,Li 7-z P.S. 6-z Br z1 Cl z2 ,Li 7-z P.S. 6-z I z1 F z2 ,Li 7-z P.S. 6-z I z1 Cl z2 ,Li 7- z P.S. 6-z I z1 Br z2 ,Li 7-v-z Na v P.S. 6-z F z1 ,Li 7-v-z Na v P.S. 6-z Cl z1 ,Li 7-v-z Na v P.S. 6-z Br z1 ,Li 7-v-z Na v P.S. 6-z I z1 ,Li 7-v-z Na v P.S. 6-z F z1 Cl z2 ,Li 7-v-z Na v P.S. 6-z F z1 Br z2 ,Li 7-v-z Na v P.S. 6-z F z1 I z2 ,Li 7-v-z Na v P.S. 6-z Cl z1 Br z2 ,Li 7-v-z Na v P.S. 6-z Cl z1 I z2 ,Li 7-v-z Na v P.S. 6-z Cl z1 F z2 ,Li 7-v-z Na v P.S.6-z Br z1 I z2 ,Li 7-v-z Na v P.S. 6-z Br z1 F z2 ,Li 7-v-z Na v P.S. 6-z Br z1 Cl z2 ,Li 7-v-z Na v P.S. 6-z I z1 F z2 ,Li 7-v-z Na v P.S. 6-z I z1 Cl z2 ,Li 7-v-z Na v P.S. 6-z I z1 Br z2 ,Li 7-v-z K v P.S. 6-z F z1 ,Li 7-v-z K v P.S. 6-z Cl z1 ,Li 7-v-z K v P.S. 6-z Br z1 ,Li 7-v-z K v P.S. 6-z I z1 ,

[0265] Li 7-v-z K v P.S. 6-z F z1 Cl z2 ,Li 7-v-z K v P.S. 6-z F z1 Br z2 ,Li 7-v-z K v P.S. 6-z F z1 I z2 ,Li 7-v-z K v P.S. 6- z Cl z1 Br z2 ,Li7-v-z K v P.S 6-z Cl z1 AND z2 ,Li 7-v-z K v P.S 6-z Cl z1 F z2 ,Li 7-v-z K v P.S 6-z No. z1 AND z2 ,Li 7-v-z K v P.S 6- z No. z1 F z2 ,Li 7-v-z K v P.S 6-z No. z1 Cl z2 ,Li 7-v-z K v P.S 6-z AND z1 F z2 ,Li 7-v-z K v P.S 6-z AND z1 Cl z2 ,Li 7-v-z K v P.S 6- z AND z1 No. z2 ,

[0266] Li 7-v-z I will v P.S 6-z F z1 ,Li 7-v-z I will v P.S 6-z Cl z1 ,Li 7-v-z I will v P.S 6-z No. z1 ,Li 7-v-z I will v P.S 6-z AND z1 ,Li 7-v- z I will v P.S 6-z F z1 Cl z2 ,Li 7-v-z I will vPS 6-z F z1 Br z2 ,Li 7-v-z With v PS 6-z F z1 and z2 ,Li 7-v-z With v PS 6-z Cl z1 Br z2 ,Li 7-v- z With v PS 6-z Cl z1 and z2 ,Li 7-v-z With v PS 6-z Cl z1 F z2 ,Li 7-v-z With v PS 6-z Br z1 and z2 ,Li 7-v-z With v PS 6-z Br z1 F z2 ,Li 7-v- z With v PS 6-z Br z1 Cl z2 ,Li 7-v-z With v PS 6-z and z1 F z2 ,Li 7-v-z With v PS 6-z and z1 Cl z2 ,Li 7-v-z With v PS 6-z and z1 Br z2 ,

[0267] them 7-2v-z Mg v PS 6-z F z1 ,Li 7-2v-z Mg v PS 6-z Cl z1 ,Li 7-2v-z Mg v PS6-z Br z1 ,Li 7-2v-z Mg v PS 6-z I z1 ,

[0268] Li 7-2v-z Mg v PS 6-z F z1 Cl z2 ,Li 7-2v-z Mg v PS 6-z F z1 Br z2 ,Li 7-2v-z Mg v PS 6-z F z1 I z2 ,Li 7-2v- z Mg v PS 6-z Cl z1 Br z2 ,Li 7-2v-z Mg v PS 6-z Cl z1 I z2 ,Li 7-2v-z Mg v PS 6-z Cl z1 F z2 ,Li 7-2v-z Mg v PS 6-z Br z1 I z2 ,Li 7-2v-z Mg v PS 6-z Br z1 F z2 ,Li 7-2v-z Mg v PS 6-z Br z1 Cl z2 ,Li 7-2v-z Mg v PS 6-z I z1 F z2 ,Li 7-2v-z Mg v PS 6-z I z1 Cl z2 ,Li 7-2v-z Mg v PS 6-z Iz1 Br z2 ,

[0269] The 7-v-z Ag v PS 6-z F z1 ,The 7-v-z Ag v PS 6-z Cl z1 ,The 7-v-z Ag v PS 6-z Br z1 ,The 7-v-z Ag v PS 6-z I z1 ,The 7-v- z Ag v PS 6-z F z1 Cl z2 ,The 7-v-z Ag v PS 6-z F z1 Br z2 ,The 7-v-z Ag v PS 6-z F z1 I z2 ,The 7-v-z Ag v PS 6-z Cl z1 Br z2 ,The 7-v- z Ag v PS 6-z Cl z1 I z2 ,The 7-v-z Ag v PS 6-z Cl z1 F z2 ,The 7-v-z Ag v PS 6-z Br z1 I z2 ,The 7-v-z Ag v PS 6-z Br z1 F z2 ,The 7-v- z Ag v PS 6-z Br z1 Clz2 ,Li 7-v-z Ag v PS 6-z I z1 F z2 ,Li 7-v-z Ag v PS 6-z I z1 Cl z2 ,and Li 7-v-z Ag v PS 6-z I z1 Br z2 ,

[0270] Wherein in the above formula, the following conditions can be independently satisfied respectively: 0 < v ≤ 0.7, 0 < z1 < 2, 0 < z2 < 1, 0 < z < 2, and z = z1 + z2; for example, 0 < v ≤ 0.7, 0 < z1 < 2, 0 < z2 ≤ 0.5, 0 < z < 2, and z = z1 + z2; 0 < v ≤ 0.3, 0 < z1 ≤ 1.5, 0 < z2 ≤ 0.5, 0.2 ≤ z ≤ 1.8, and z = z1 + z2; 0 < v ≤ 0.05, 0 < z1 ≤ 1.5, 0 < z2 ≤ 0.2, 1.0 ≤ z ≤ 1.8, and z = z1 + z2; or 0 < v ≤ 0.05, 0 < z1 ≤ 1.5, 0 < z2 ≤ 0.2, 1.0 ≤ z ≤ 1.5, and z = z1 + z2. When v, z1 or z2 does not exist in the above formula, v = 0, z1 = 0, or z2 = 0. For example, when z1 = 0, z = z2. For example, when z2 = 0, z = z1.

[0271] The compound represented by Formula 8 can belong to, for example, the cubic crystal system, and more particularly to the F-43m space group. In addition, the compound represented by Formula 8 can be a thiogermanate-type sulfide having a thiogermanate crystal structure. The compound represented by Formula 8 includes, for example, one or more of monovalent cation elements and divalent cation elements that replace a part of the lithium sites in the thiogermanate crystal structure, or includes heterogeneous halogen elements, or includes substituted SO n anions in the halogen sites, and thus, the lithium ion conductivity can be further improved, and the electrochemical stability against lithium metal can be further improved. As used herein, "thiogermanate" or "thiogermanate-type" means that the compound has a crystal structure isomorphic to that of thiogermanate Ag8GeS6.

[0272] The compound represented by Formula 8 is, for example, Li6PS5Cl.

[0273] The sulfide-based solid electrolyte used herein can be a thiogermanate-type compound including one or more of the following: Li 7-x PS 6-x Cl x, 0≤x≤2; Li 7-x PS 6-x Br x , 0≤x≤2; or Li 7-x PS 6-x I x wherein x satisfies the condition of 0≤x≤2. In particular, the sulfide-based solid electrolyte included in the solid electrolyte may be an argyrodite-type compound including one or more of the following: Li6PS5Cl, Li6PS5Br, or Li6PS5I.

[0274] The example of polymer solid electrolyte is polyethylene oxide, polypropylene oxide, polystyrene (PS), polyphosphazene, polysiloxane, polyvinylidene fluoride-to-hexafluoropropylene (PVDF-HFP), polyacrylonitrile (PAN) or its combination. The ionic conductivity of the polymer solid electrolyte can be realized by the local segment motion of polymer. The polymer solid electrolyte can be prepared by mixing polyether with plasticizer salt and sometimes some liquid plasticizers. Solvent evaporation coating method can be used to prepare the electrolyte into film. However, it is not limited to this, and any suitable polymer solid electrolyte available in the art can be used.

[0275] If necessary, the solid electrolyte layer may further include a binder. The binder included in the solid electrolyte layer 30 may be, for example, styrene-butadiene rubber (SBR), polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, etc., but is not limited to these. The binder may be any suitable material that can be used as a binder in the relevant technical field.

[0276] The solid electrolyte layer 30 can be prepared by depositing using a known film forming method such as an aerosol deposition method, a cold spray method, or a sputtering method. In some embodiments, the solid electrolyte layer 30 can be prepared by pressing particles of a single solid electrolyte. In some embodiments, the solid electrolyte layer 30 can be prepared by mixing a solid electrolyte, a solvent, and a binder, applying the mixture, and drying and pressing.

[0277] like Figure 4 As shown in , the plating film (e.g., film) 24 may be disposed (e.g., formed) on the surface of the negative electrode current collector 21. The film 24 may include an element that can form an alloy with lithium. The element that can form an alloy with lithium may include, for example, gold, silver, zinc, tin, indium, silicon, aluminum, or bismuth. The film 24 may be composed of one of these metals or may be composed of an alloy of several types of metals.

[0278] pass Figure 4 The presence of the plating film 24 shown in Figure 5The deposition form of the metal layer 23 shown in FIG. 1 can be further flattened, and the characteristics of the all-solid-state secondary battery 1 can be further improved. Figure 5 The metal layer 23 shown in FIG. 2 may be formed between the negative electrode current collector 21 and the negative electrode active material layer 22 by overcharging the negative electrode active material layer 22. Alternatively, Figure 5 The metal layer 23 shown in FIG. 1 is formed in advance (ie, before initial charge) between the negative electrode current collector 21 and the negative electrode active material layer 22 .

[0279] Figure 5 The metal layer 23 shown in the figure may include lithium or a lithium alloy. That is, the metal layer 23 may function as a lithium reservoir. The lithium alloy may be, for example, a Li-Al alloy, a Li-Sn alloy, a Li-In alloy, a Li-Ag alloy, a Li-Au alloy, a Li-Zn alloy, a Li-Ge alloy, a Li-Si alloy, etc. Figure 5 The metal layer 23 shown in FIG. 4 may be formed of one of these alloys or lithium, or an alloy thereof.

[0280] The thickness of the metal layer 23 may range from about 1 μm to about 200 μm, but is not particularly limited. When the thickness of the metal layer 23 is less than 1 μm, the function of the metal layer 23 as a reservoir may not be fully presented. When the thickness of the metal layer 23 is greater than 200 μm, the mass and volume of the all-solid-state secondary battery 1a may increase, resulting in significantly deteriorated characteristics. The metal layer 23 may be, for example, a metal foil having a thickness within the range described above.

[0281] The thickness of the film 24 may be about 1 nm to about 500 nm, for example, about 10 nm to about 400 nm, about 30 nm to about 300 nm, or about 50 nm to about 200 nm, but is not limited thereto. When the thickness of the film 24 is within this range, the function of the film 24 is fully exercised and the amount of lithium precipitated in the negative electrode layer is appropriate, so that the characteristics of the all-solid-state secondary batteries 1 and 1a are improved. The film 24 can be formed on the negative electrode current collector 21 by, for example, vacuum deposition, sputtering, or plating.

[0282] Method for preparing hybrid solid-state ion conductor

[0283] According to another aspect of the present disclosure, a method for manufacturing a hybrid solid-state ion conductor includes: preparing a precursor and a salt for forming a solid-state ion conductor; providing a precursor mixture for forming a solid-state ion conductor by mechanically grinding the precursor and the salt for forming a solid-state ion conductor; and shaping the precursor mixture for forming a solid-state ion conductor to prepare the hybrid solid-state ion conductor.

[0284] In one aspect, a method of preparing a hybrid solid-state ion conductor comprises:

[0285] providing precursors and salts for forming a solid-state ion conductor;

[0286] mechanically grinding the precursor and the salt to provide a precursor mixture; and

[0287] The precursor mixture is shaped to thereby prepare the hybrid solid-state ion conductor.

[0288] The hybrid solid-state ion conductor may include a compound represented by Formula 1 and a salt represented by Formula 2:

[0289] Formula 1

[0290] M a M' b X c Y' d Z e

[0291] in

[0292] M may be an alkali metal having an oxidation number of +1,

[0293] M' may be one or more metal cations having an oxidation number of +2, +3, +4, +5, or +6,

[0294] X can be one or more halogen anions,

[0295] Y' may be an anion having an oxidation number of -1,

[0296] Z may be an anion having an oxidation number of -3,

[0297] 0.5 ≤ a ≤ 7, 0.5 ≤ b ≤ 2, 0 < c ≤ 6, 0 ≤ d ≤ 6, 0 ≤ e ≤ 6, and

[0298] 0 < c + d + e ≤ 6,

[0299] Formula 2

[0300] M" f (PO4) g

[0301] M" may be the same metal cation as M' in Formula 1 or a different metal cation having an ionic radius within ±10% of the ionic radius of M', and

[0302] 0 < f ≤ 3, and 0 < g ≤ 10.

[0303] The method of making the hybrid solid-state ion conductor allows the preparation of ion conductors with improved ionic conductivity, electrochemical stability over a wide potential window when applied as solid-state electrolytes in electrochemical devices, improved cycling stability towards metal electrodes including lithium, and reversible development of designed positive electrode capacity.

[0304] When preparing a precursor mixture for forming a solid ion conductor, an M precursor, an M' precursor, an X precursor, a Y' precursor salt, a Z precursor salt, and a salt of Formula 2 may be mixed together. The M precursor may be a precursor of an alkali metal element having an oxidation number of +1, and the M' precursor may be a precursor of a metal element having an oxidation number of +3 or +4.

[0305] The M precursor and the M' precursor may include halides of the M metal and the M' metal, such as chlorides, oxides, nitrides, oxynitrides, nitrates, hydroxides, and carbonates, respectively. For example, the M' precursor may include chlorides, oxides, nitrides, oxynitrides, nitrates, hydroxides, and carbonates of the following elements: Ti, Zr, Hf, V, Nb, Ta, Al, Ga, In, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Y, Lu, or combinations thereof. For example, the M' precursor may include chlorides of Ti, Zr, Hf, V, Nb, Ta, Al, Ga, In, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Y, Lu, or combinations thereof. In some embodiments, the Y' precursor salt may be a salt comprising one or more of the following anions: SO3 - 、CH3COO - , CN - 、NO3 - 、NO2 - 、H2PO4 - PF6 - OH - 、BF4 - 、N(CF3SO2)2 - CF3CO2 - CF3SO3 - 、C(CF3SO2)3 - 、HCO3 - 、ClO4 - 、HSO4 - , or SCN - The Z precursor salt may be a salt comprising one or more of the following anions: (BO4) 3- 、(BO3) 3- 、(PO4) 3-, [Fe(CN)6] 3- , or [Ag(S2O3)2] 3- In some embodiments, M" as the cation of the salt of Formula 2 may be the same metal cation as M' in Formula 1 or a different metal cation having an ionic radius difference from M' within ±10%.

[0306] The precursor for forming a solid ion conductor and the salt may be contacted in suitable amounts, such as stoichiometric amounts, to prepare a mixture. The mixture is mechanically ground.

[0307] The mechanical grinding can be carried out using a ball mill, an air jet mill, a bead mill, a roller mill, a planetary mill, a manual grinding, a high energy ball mill, a planetary grinding ball mill, a stirring ball mill, a vibration mill, a mechanical fusion grinding, a shaking table grinding, a planetary grinding, a grinder grinding, a disc grinding, a shape grinding, a nauta grinding, a nobilta grinding, a high speed mixer or a combination thereof. For example, the mechanical grinding can be planetary grinding and can be carried out at room temperature. After carrying out the mechanical grinding, molding can be further included.

[0308] After the mechanical grinding, a resting process may be further included. For example, the resting process may be performed at room temperature for 1 minute to 10 minutes.

[0309] Hereinafter, embodiments and comparative examples of the present disclosure will be described. However, the following embodiments are merely examples of the present disclosure, and the present disclosure is not limited to the following embodiments.

[0310] Example

[0311] (Hybrid Solid State Ion Conductor)

[0312] Example 1: Preparation of a mixed solid ion conductor of 6Li2ZrCl6 and Zr3(PO4)4

[0313] ZrCl4 and Li3(PO4) are added to the reactor in a stoichiometric ratio of 9:4 and mixed to prepare a precursor mixture for forming a solid-state ion conductor. The precursor mixture for forming a solid-state ion conductor is repeatedly mixed for 15 minutes at 600 rpm using a planetary mill (Pulverisette 7 premium line) loaded with 10 millimeters (mm) diameter zirconium oxide (YSZ) balls, and rested for 5 minutes. This cycle is implemented for a total of 24 hours to obtain a precursor mixture. The precursor mixture is placed in a pelletizer with a diameter of 1 inch, and a uniaxial pressure is used to apply a weight of 5 tons to it for 2 minutes to manufacture a disc-shaped 6Li2ZrCl6 and Zr3(PO4)4 mixed solid-state ion conductor disc (disc).

[0314] Example 2: Mixed solid ion conductor with 4.75Li2ZrCl6, 0.75Zr3(PO4)3, and 0.25ZrCl4 impurities preparation

[0315] A mixed solid ion conductor disc of 4.5Li2ZrCl6, 0.75Zr3(PO4)3, and 3 wt% ZrCl4 impurity was prepared in the same manner as in Example 1, except that the ZrCl4 and Li3(PO4) were adjusted to a stoichiometric ratio of 7:3 in the reactor.

[0316] Example 3: Preparation of a mixed solid ion conductor of 15LiTaCl6 and Ta3(PO4)5

[0317] A mixed solid ion conductor disc of 15LiTaCl6 and Ta3(PO4)5 was prepared in the same manner as in Example 1, except that TaCl5 and Li3(PO4) were adjusted to a stoichiometric ratio of 18:5 in the reactor.

[0318] Example 4: Preparation of a mixed solid ion conductor of Li3YCl6 and YPO4

[0319] A mixed solid ion conductor disc of Li3YCl6 and YPO4 was prepared in the same manner as in Example 1, except that YCl3 and Li3(PO4) were adjusted to a stoichiometric ratio of 1:1 in the reactor.

[0320] Example 5: Preparation of a mixed solid ion conductor of Li2ZrCl6, Zr3(PO4)4, and LaPO4

[0321] A mixed solid ion conductor of Li2ZrCl6, Zr3(PO4)4, and LaPO4 was prepared in the same manner as in Example 1, except that the stoichiometric ratio of ZrCl4, LiCl, and La(PO4) was adjusted to 45:20:1 in the reactor.

[0322] Comparative Example 1: Preparation of solid-state ion conductor of Li2ZrCl6

[0323] A solid ion conductor pellet of Li2ZrCl6 was prepared in the same manner as in Example 1, except that ZrCl4 and LiCl were adjusted to a stoichiometric ratio of 1:2 in the reactor.

[0324] Comparative Example 2: Preparation of a solid ion conductor of LiTaCl6

[0325] A solid ion conductor pellet of LiTaCl 6 was prepared in the same manner as in Example 1, except that TaCl 5 and LiCl were adjusted to a stoichiometric ratio of 1:1 in the reactor.

[0326] Comparative Example 3: Preparation of Li3YCl6 solid ion conductor

[0327] A solid ion conductor disc of Li3YCl6 was prepared in the same manner as in Example 1, except that YCl3 and LiCl were adjusted to a stoichiometric ratio of 1:3 in the reactor.

[0328] Comparative Example 4: Preparation of solid-state ion conductor of Li3PO4

[0329] A solid ion conductor pellet of Li3PO4 was prepared in the same manner as in Example 1, except that Li3(PO4) was added to the reactor.

[0330] Comparative Example 5: Li2ZrCl6 and Li 1.3 Al 0.3 Ti 1.7 Preparation of mixed solid-state ion conductors of (PO4)3

[0331] Li2ZrCl6 and Li 1.3 Al 0.3 Ti 1.7 (PO4)3 mixed solid ion conductor disc, except that ZrCl4, LiCl and Li 1.3 Al 0.3 Ti 1.7 (PO4)3 was adjusted to a stoichiometric ratio of 1:2:0.2.

[0332] Comparative Example 6: Li 2.2 Ho 0.2 Zr 0.8 Preparation of solid-state ion conductor of Cl6

[0333] A solid ion conductor pellet was prepared in the same manner as in Example 1, except that LiCl, HoCl 3 , and ZrCl 4 were adjusted to a stoichiometric ratio of 2.2:0.2:0.8 in the reactor.

[0334] Comparative Example 7: Preparation of solid ion conductor of Li6PS5Cl

[0335] A solid ion conductor pellet was prepared in the same manner as in Example 1, except that Li2S, P2S5, and LiCl were adjusted to a stoichiometric ratio of 5:1:2 in the reactor.

[0336] Comparative Example 8: Preparation of a mixed solid ion conductor containing 6Li2ZrCl6, Zr3(PO4)4, and Li3PO4 impurities

[0337] A mixed solid ion conductor disc of 6Li2ZrCl6, Zr3(PO4)3, and 5 wt% Li3PO4 impurity was prepared in the same manner as in Example 1, except that ZrCl4 and Li3(PO4) were adjusted to a stoichiometric ratio of 9:5 in the reactor.

[0338] Comparative Example 9: Preparation of a mixed solid ion conductor of 4Li2ZrCl6 and Li3PO4

[0339] A mixed solid ion conductor disc of 4Li2ZrCl6 and Li3PO4 was prepared in the same manner as in Example 1, except that ZrCl4, LiCl, and Li3(PO4) were adjusted to a stoichiometric ratio of 4:8:1 in the reactor.

[0340] Comparative Example 10: Preparation of a mixed solid ion conductor of 8Li2ZrCl6 and Ca3(PO4)2

[0341] A mixed solid ion conductor disc of 8Li2ZrCl6 and Ca3(PO4)2 was prepared in the same manner as in Example 1, except that the stoichiometric ratio of ZrCl4, LiCl, and Ca3(PO4)2 was adjusted to 8:16:1 in the reactor.

[0342] (All-solid-state secondary battery)

[0343] Example 6: Fabrication of an all-solid-state secondary battery

[0344] (Positive electrode layer manufacturing)

[0345] A 10 µm thick copper current collector was placed on the bottom of a tubular battery case having an inner diameter of 13 mm, and a 20 µm thick indium (In) deposited foil was placed on a surface of the copper current collector to prepare a negative electrode layer.

[0346] (Manufacturing of negative electrode layer / solid electrolyte layer stack)

[0347] On the negative electrode layer, 70 milligrams (mg) of Li6PS5Cl solid ion conductor discs (Mitusi, S33) were placed as the first solid electrolyte layer and the pressure was evenly distributed thereon. On the first solid electrolyte layer, 30 mg of the mixed solid ion conductor discs of 6Li2ZrCl6 and Zr3(PO4)4 prepared in Example 1 were placed as the second solid electrolyte layer and the pressure was evenly distributed thereon, and then, 250 megapascals (MPa) were applied by cold isostatic pressing (CIP) at 25°C to prepare a stack (thickness: about 300 µm) having a copper current collector layer / indium (In) layer / Li6PS5Cl first solid electrolyte layer / 6Li2ZrCl6 and Zr3(PO4)4 second solid electrolyte layer.

[0348] (Manufacturing of positive electrode layer)

[0349] LiNi as the positive electrode active material 0.9 Co 0.07 Mn 0.03O2 (NCM), the mixed solid ion conductor disc prepared in Example 1 as a solid electrolyte, and carbon nanofiber (CNF) as a conductive agent were mixed in a mass ratio of 85:23:1. 42 mg of the mixture was placed on an aluminum foil current collector having a thickness of 18 μm, thereby completing the preparation of the positive electrode layer.

[0350] (Manufacturing of all-solid-state secondary batteries)

[0351] The positive electrode layer was placed on the stack of negative electrode layer / solid electrolyte layer and a weight of 4 tons was applied thereto for 2 minutes to manufacture a torque battery type all-solid-state secondary battery.

[0352] Examples 7 to 10: Fabrication of all-solid-state secondary batteries

[0353] An all-solid-state secondary battery is manufactured in the same manner as in Example 6, except that the mixed solid-state ion conductor disc prepared according to Examples 2 to 5 is used as the second solid-state electrolyte when preparing a stack of negative electrode layer / solid-state electrolyte layer, and is used as a solid-state electrolyte when manufacturing a positive electrode layer.

[0354] Comparative Examples 11 to 20: Manufacturing of All-Solid-State Secondary Batteries

[0355] An all-solid-state secondary battery is manufactured in the same manner as in Example 6, except that the (mixed) solid-state ion conductor discs prepared in Comparative Examples 1 to 10 are used as the second solid-state electrolyte when manufacturing the negative electrode layer / solid-state electrolyte layer stack, and as the solid-state electrolyte when manufacturing the positive electrode layer.

[0356] Evaluation Example 1: XRD Analysis

[0357] The mixed solid ion conductor and Zr3(PO4)4 prepared in Example 1 were subjected to XRD spectrum analysis using CuKα radiation. The XRD spectrum analysis was performed at a diffraction angle 2θ ranging from 10°2θ to 60°2θ at 1° / min. The results are shown in Figure 6 middle.

[0358] refer to Figure 6 , the hybrid solid-state ion conductor prepared in Example 1 has a main peak in the region of diffraction angle 2θ of 15°2θ to 25°2θ, and a secondary peak in the region of diffraction angle 2θ of 25°2θ to 35°2θ. This result is the same as the XRD spectrum of Zr3(PO4)4.

[0359] From this result, it was confirmed that the mixed solid-state ion conductor prepared in Example 1 included Zr3(PO4)4.

[0360] Evaluation Example 2: Interface Resistance Experiment

[0361] A lithium foil having a thickness of 8 millimeters (mm) was placed on the surface of the (hybrid) solid-state ion conductor disc prepared in Example 1 and Comparative Example 1, and 250 MPa was applied thereto by CIP at 25°C. A lithium electrode was attached to the other surface of the disc in the same manner to prepare a lithium symmetric battery having a structure of lithium / (hybrid) solid-state ion conductor disc / lithium. Current collectors were respectively placed on the lithium electrodes provided on the surface of the disc, and while the symmetric battery was sealed, a portion of each of the current collectors protruded to the outside of the sealed symmetric battery and served as an electrode terminal. The interface resistance of the disc was measured using the prepared symmetric battery.

[0362] The impedance of the symmetrical cell was measured using a 2-probe method using a Biologic VMP3 as an impedance analyzer. Impedance measurements were performed at 25°C in a dry room atmosphere with an amplitude of 200 millivolts (mV), a frequency in the range of 1 Hz to 1 megahertz (MHz), and a dew point of -60°C. The interfacial resistance was measured by the size of the arc of the Nyquist plot for the impedance measurement results. The results are shown in Figure 7 middle.

[0363] refer to Figure 7 The interface resistance of the solid ion conductor prepared in Comparative Example 1 is 430 Ω·cm 2 The interface resistance of the mixed solid-state ion conductor prepared in Example 1 is 120 Ω·cm 2 or less and is significantly reduced by about 72.1% compared with the solid ion conductor prepared in Comparative Example 1.

[0364] Evaluation Example 3: Ion conductivity and activation energy experiments

[0365] The (hybrid) solid ion conductor discs having a thickness of about 1000 μm prepared in Example 1 and Comparative Example 1 were prepared. Platinum (Pt) paste having a thickness of 20 nm was deposited by sputtering on both surfaces of the (hybrid) solid ion conductor discs to form platinum (Pt) electrodes. Wires were connected to the platinum (Pt) electrodes on the surfaces of the specimens, and they were analyzed using electrochemical impedance spectroscopy (EIS).

[0366] With an amplitude of approximately 10 mV and a range from 1 Hz to 10 6The EIS analysis was performed at a frequency of 1.5 Hz. As an impedance analyzer, 2 probes (potentiostat / galvanostat and 1455 frequency response analyzer (FRA) multi-channel test module, Solartron Analytical, UK) were used as impedance analyzer. The impedance of the wafer was measured at room temperature (25 ° C) using a probe method. Resistance values ​​were obtained by the arc of the Nyquist diagram for impedance measurement results, from which conductivity was calculated by correcting electrode area and wafer thickness. The results are shown in Table 1.

[0367] Table 1

[0368]

[0369] *The weight % is based on the total weight of the hybrid solid-state ion conductor of 100 weight %.

[0370] Referring to Table 1, the ionic conductivity of each of the mixed solid-state ion conductors prepared by Examples 1-5 is at least 8.1× 10 -4 S cm -1 , which is greater than the ionic conductivity of the mixed solid-state ion conductors prepared by Comparative Examples 5, 8, 9, and 10. Among these, the ionic conductivity of the mixed solid-state ion conductor prepared in Example 1 is very high, at 2.0 × 10 -3 S cm -1 In addition, compared with the halide-based compound solid-state ion conductors prepared in Comparative Examples 1 to 3, 6, and 7, the hybrid solid-state ion conductors prepared in Examples 1 to 5 have greater or comparable ion conductivities.

[0371] In addition, when measuring EIS, the activation energy (E) for conductivity is calculated from the structure measured as follows a ) value: changing the temperature of the chamber in which each sample is loaded. E was calculated from the slope value by converting the conductivity values ​​measured at each temperature in the range of 273 K to 398 K into the Arrhenius plot (Ln(σT) vs. 1 / T) of Equation 1. a In this regard, conductivity refers to ionic conductivity. The results are shown in Figure 8 middle.

[0372] Equation 1

[0373] σT = A exp(E a / RT)

[0374] in

[0375] E a is the activation energy, T denotes the absolute temperature, A denotes the pre-exponential factor, R denotes the gas constant, and σ denotes the conductivity.

[0376] refer to Figure 8 , the activation energy of the solid-state ion conductor prepared in Comparative Example 1 is 0.36 eV. The activation energy of the hybrid solid-state ion conductor prepared in Example 1 is 0.19 eV and is significantly reduced by about 47% compared with the solid-state ion conductor prepared in Comparative Example 1.

[0377] Evaluation Example 4: Initial charge / discharge experiment

[0378] The all-solid-state secondary batteries manufactured in Example 6 and Comparative Example 17 were subjected to charging and discharging experiments in a constant temperature bath at 25° C. as follows.

[0379] Each all-solid-state secondary battery was charged at a constant current of 0.1 C until the battery voltage reached 4.0 V, and at a constant voltage of 4.0 V until the current value reached 0.1 C. The C rate is the discharge rate of the battery and is obtained by dividing the total capacity of the battery by the total discharge time of 1 hour, for example, the C rate of a battery with a discharge capacity of 1.6 ampere hours will be 1.6 amperes. The total capacity is determined by the discharge capacity at the 1st cycle. 0.1 C or C / 10 refers to the current that completely discharges the battery in 10 hours.

[0380] Next, discharge was performed at a constant current of 0.1 C until the battery voltage reached 2.0 V. The results of the initial charge and discharge experiments are shown in Fig. 9A and 9B In addition, the discharge capacity obtained from the experimental results was divided by the charge capacity and multiplied by 100%, and the obtained value was regarded as the coulombic efficiency (%).

[0381] refer to Fig. 9A and 9B The discharge capacity of the all-solid-state secondary battery manufactured in Example 6 is 3.8 mAh cm -2 , which is 0.3 mAh cm greater than the discharge capacity of the all-solid-state secondary battery manufactured in Comparative Example 17. -2 In addition, the coulombic efficiency of the all-solid-state secondary battery manufactured in Example 6 was about 92% and was about 13% greater than the coulombic efficiency of the all-solid-state secondary battery manufactured in Comparative Example 17.

[0382] This result confirms that the initial charge and discharge performance of the all-solid-state secondary battery including the mixed solid-state ion conductor prepared in Example 1 is greater than the initial charge and discharge performance of the all-solid-state secondary battery including the Li6PS5Cl halide-based compound prepared in Comparative Example 7 alone as a solid-state ion conductor.

[0383] A hybrid solid-state ion conductor according to one aspect includes a compound represented by Formula 1 and a salt represented by Formula 2. Due to the mixing of metal phosphate excluding alkali metals, the hybrid solid-state ion conductor can provide a solid-state electrolyte, a positive electrode, and an electrochemical device each having higher ion conductivity, improved charge and discharge characteristics, compared to a case in which a halide-based solid-state ion conductor is used alone.

[0384] It should be understood that the embodiments described herein should be considered in a descriptive sense only and not for limiting purposes. The description of features or aspects in each embodiment should typically be considered to be applicable to other similar features or aspects in other embodiments. Although one or more embodiments have been described with reference to the accompanying drawings, it will be understood by those of ordinary skill in the art that various changes in form and detail may be made therein without departing from the spirit and scope as defined by the following claims.

Claims

1. Hybrid solid-state ion conductors, including: A compound represented by Formula 1; and A salt represented by Formula 2, Formula 1 M a M' b X c Y' d Z e In formula 1, M is an alkali metal having an oxidation number of +1, M' is one or more metal cations having an oxidation number of +2, +3, +4, +5, or +6, X is one or more of halogen anions having an oxidation number of -1, Y' is an anion having an oxidation number of -1, Z is an anion having an oxidation number of -3, 0.5 ≤ a ≤ 7, 0.5 ≤ b ≤ 2, 0 < c ≤ 6, 0 ≤ d ≤ 6, 0 ≤ e ≤ 6, and 0 < c + d + e ≤ 6, and Formula 2 M" f (PO4) g In Formula 2, M" is the same metal cation as M' in Formula 1, or a different metal cation having an oxidation number of +2, +3, +4, +5, or +6 and having an ionic radius within ±10% of the ionic radius of M', 0 < f ≤ 3, and 0 < g ≤ 10. 2 . The hybrid solid-state ion conductor of claim 1 , wherein the metal cation of M′ in Formula 1 has an ionic radius of 70 picometers to 100 picometers.

3. The hybrid solid-state ion conductor of claim 1, wherein M' in Formula 1 is one or more of Ti, Zr, Hf, V, Nb, Ta, Al, Ga, In, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Y, or Lu.

4. The hybrid solid-state ion conductor as claimed in claim 1, wherein Y' in Formula 1 is one or more of the following: SO3 - 、CH3COO - , CN - 、NO3 - 、NO2 - 、H2PO4 - PF6 - OH - 、BF4 - 、N(CF3SO2)2 - CF3CO2 - CF3SO3 - 、C(CF3SO2)3 - 、HCO3 - 、ClO4 - 、HSO4 - , or SCN - .

5. The hybrid solid-state ion conductor of claim 1, wherein Z in Formula 1 is one or more of the following: (BO4) 3- 、(BO3) 3- 、(PO4) 3- , [Fe(CN)6] 3- , or [Ag(S2O3)2] 3- .

6. The hybrid solid-state ion conductor of claim 1, wherein the hybrid solid-state ion conductor does not include a first component, the first component includes a compound represented by Formula 3, a salt represented by Formula 4, or a combination thereof, Formula 3 (M1) p (X1) q (Y'1) r (Z1) s In formula 3, M1 is one or more metal cations having an oxidation number of +2, +3, +4, +5, or +6, X1 is one or more of halogen anions having an oxidation number of -1, Y'1 is an anion having an oxidation number of -1, Z1 is an anion having an oxidation number of -3, and 0.5 ≤ p ≤ 2, 0 < q ≤ 6, 0 ≤ r ≤ 6, 0 ≤ s ≤ 6, and 0 < q + r + s ≤ 6, Formula 4 <h2 style=";text-align:left;direction:ltr">(M2)<h2 style=";text-align:left;direction:ltr"> t <h2 style=";text-align:left;direction:ltr"> (PO4)<h2 style=";text-align:left;direction:ltr"> v In formula 4, M2 is an alkali metal having an oxidation number of +1, 0.5 ≤ t ≤ 7, and 0 < v ≤ 7 / 3.

7. The hybrid solid-state ion conductor of claim 1, further comprising a first component, wherein the amount of the first component is greater than 0 wt % and less than 5 wt % based on 100 wt % of the total weight of the hybrid solid-state ion conductor, wherein the first component comprises a compound represented by Formula 3, a salt represented by Formula 4, or a combination thereof, Formula 3 (M1) p (X1) q (Y'1) r (Z1) s In formula 3, M1 is one or more metal cations having an oxidation number of +2, +3, +4, +5, or +6, X1 is one or more of halogen anions having an oxidation number of -1, Y'1 is an anion having an oxidation number of -1, Z1 is an anion having an oxidation number of -3, and 0.5 ≤ p ≤ 2, 0 < q ≤ 6, 0 ≤ r ≤ 6, 0 ≤ s ≤ 6, and 0 < q + r + s ≤ 6, Formula 4 <h2 style=";text-align:left;direction:ltr">(M2)<h2 style=";text-align:left;direction:ltr"> t <h2 style=";text-align:left;direction:ltr"> (PO4)<h2 style=";text-align:left;direction:ltr"> v In formula 4, M2 is an alkali metal having an oxidation number of +1, 0.5 ≤ t ≤ 7, and 0 < v ≤ 7 / 3.

8. The hybrid solid-state ion conductor of claim 1, wherein the compound of Formula 1 and the salt of Formula 2 are each nanoparticles having a particle size of 1 nm to 100 nm.

9. The hybrid solid-state ion conductor of claim 1, wherein the hybrid solid-state ion conductor has a distorted rock-salt type crystal structure.

10. The hybrid solid-state ion conductor of claim 1, wherein The compound of formula 1 has an octahedral structure as follows: wherein M' is a central metal cation coordinated by six halogen anions, wherein each halogen anion is optionally replaced by one or more of Y' or Z, and The salt of Formula 2 is located in the space around the octahedral structure.

11. The hybrid solid-state ion conductor according to claim 1, wherein in the hybrid solid-state ion conductor, one of the compound represented by Formula 1 and the salt represented by Formula 2 has a layered crystal structure. 12 . The hybrid solid-state ion conductor of claim 1 , wherein an amount of the salt of Formula 2 is 5 wt % to 30 wt % based on 100 wt % of the total weight of the hybrid solid-state ion conductor.

13. The hybrid solid-state ion conductor of claim 1, wherein the hybrid solid-state ion conductor has a 8 x 10 -4 Siemens / cm to 3 x 10 -3 Ionic conductivity in Siemens / cm.

14. A solid electrolyte comprising the mixed solid ion conductor according to any one of claims 1 to 13.

15. A positive electrode comprising the hybrid solid-state ion conductor according to any one of claims 1 to 13.

16. An electrochemical device comprising: positive electrode layer; Negative electrode layer; as well as a solid electrolyte layer between the positive electrode layer and the negative electrode layer, The solid electrolyte as claimed in claim 14 is in at least one of the positive electrode layer, the negative electrode layer, or the solid electrolyte layer.

17. The electrochemical device of claim 16, wherein The positive electrode layer includes the solid electrolyte, and The solid electrolyte layer comprises: A first solid electrolyte including the solid electrolyte, and a second solid electrolyte including a sulfide-containing solid electrolyte, an oxide-containing solid electrolyte, a polymer solid electrolyte, or a combination thereof.

18. The electrochemical device of claim 16, wherein the electrochemical device is an electrochemical cell, a battery, a supercapacitor, a fuel cell, a sensor, or a color-changing device.

19. A method for preparing a hybrid solid-state ion conductor, the method comprising: providing precursors and salts for forming a solid-state ion conductor; mechanically grinding the precursor and the salt to provide a precursor mixture; and The precursor mixture is shaped to thereby prepare the hybrid solid-state ion conductor according to any one of claims 1 to 13.

Citation Information

Patent Citations

  • wireless communication device

    KR1020230129565A